Strip rotation intercropping enhances maize yield while improving soil quality in soybean strips in semi-arid Northeast China - Shuo Liu; Yuting Zheng; Yun Gu; Rui Liao; Bowei Duan; Jiajun Lin; Zhe Zhang; Wei Bai; Yuanquan Chen; Peng Sui (Soil and Tillage Research, 2026)

Enhanced carbon capture and storage in the green microalga Chlamydomonas by heterologous expression of an engineered carbonic anhydrase - Yunlong Ge; Wanyi Zhang; Shuo Lin; Xinyu Mao; Keqing Liu; Wei Ma; Songlin Ma; Yanbo Liu; Zhanyou Chi; Fantao Kong (Bioresource Technology, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Molecular characterization and preliminary functional analysis of the NLRP3 inflammasome in golden pompano (Trachinotus ovatus) in response to Streptococcus agalactiae infection - Zhengjing Lin; Xuemei Mou; Peng Xu; Kianann Tan; Ting Huang; Renjie Li; Shuo Hu; Xiaoxin Huang; Sisi Huang; Lanfang Dong; Xiaohui Cai (Fish & Shellfish Immunology, 2026)

Assessment of reproductive risks of bisphenol S in male BALB/c mice through functional histological and multi-omics investigations - Xiaotan Lin; Huan Liu; Wei Ma; Shuo Lu; Bo Li; Wen Zhang; Ning Li; Tingting Chen (Food and Chemical Toxicology, 2026)

SERS sensing platform based on MIL-100(Fe)@AgNPs for norepinephrine/adenosine monitoring in patient plasma - Peng Zhao; Kai Liu; Yueyan Li; Xiaofang Ban; Yuheng Wu; Jiaqi Liu; Xiaohong Wu; Ziyi Cheng; Fan Wang; Shuo Li; Feng Lin; Huifang Tang; et al. (Analytica Chimica Acta, 2026)

Prokaryotic Argonautes as programmable tools for foodborne biological hazards detection: mechanisms, applications, and prospects - Jing-bo Jiao; Cheng-long Zhao; Jiang-li Cao; Tong Lin; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Critical Reviews in Food Science and Nutrition, 2026)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

Identification of GhREC1334 as a novel nuclear-localized adenylate cyclase associated with photosynthetic performance in cotton - Shuo Cao; Lin Li; Binghua Li; Shi Xu; Hanfeng Zhang; Ruqiang Xu (South African Journal of Botany, 2026)

Diverging hydrometeorological drivers of flashier floods in a warming climate - Fengjia Zhou; Shuo Wang; Louise Slater; Peirong Lin; Hanbo Yang; Sijie Tang; Amir AghaKouchak (Journal of Hydrology, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Cepharanthine-mediated photodynamic inactivation and active gelatin packaging for pork preservation - Lin Yang; Kaiyuan Su; Zhuoran Guo; Bingzhi Li; Yajie Wang; Zhenqing Guo; Jianlong Wang; Shuo Shi; Shusen Li; Shengpeng Su; Wentao Zhang (Food Research International, 2026)

An integrated litmus test platform for low-background detection and photothermal inactivation of Salmonella typhimurium via HCR-urease signal amplification - Qing Kang; Tong Lin; Jingbo Jiao; Xinjun Du; Shuo Wang (Food Chemistry, 2026)

Process-dependent structural and functional modification of yeast protein: Alkaline extraction-acid precipitation versus high-pressure homogenization-assisted pH shifting - Lin Li; Xiaoyu Ma; Dan Huang; Ming Du; Shuo Wan; Shuzhen Cheng (Food Chemistry, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

Enhanced phenanthrene degradation in microalgae-bacteria systems: Mechanistic roles of exogenous and indigenous degraders - Mengying Wang; Han Wang; Xuetao Liang; Jingran Li; Chen Wang; Longyan Cui; Shuo Yang; Jiaxuan Lin; Qi Yang; Zhilin Yang (Bioresource Technology, 2026)

From fermentation to function: a critical review of lactic acid bacteria redesign for functional foods and precision nutrition - Jianwei Zang; Luyao Xiao; Xiaogan Zhao; Yibo Shi; Kai Ma; Changliang Zhang; Shuo Geng; Xin Rui; Tao Lin; Wei Li (Critical Reviews in Food Science and Nutrition, 2026)

Future climate and land-use change reshape watershed best management practices portfolio for nutrient control - Yuanxin Ren; Hangzhen Zhang; Shuo Cheng; Bingqian Liu; Lin Ji; Jun Xia; Dandong Cheng (Journal of Hydrology, 2026)

Average photon energy based solar spectrum reconstruction for building-oriented TMY databases - Shuo Ma; Yanyun Zhang; Jingchao Xie; Yupeng Wu; Haifeng Wu; Peng Xue; Lin Li (Journal of Cleaner Production, 2026)

Gadolinium-based metal-organic framework with restriction of aggregation-caused quenching effect synergized high-activity pt-single-atom catalyst for multiplex self-enhanced electrochemiluminescence sensing detection of kanamycin - Ling Wu; Kaiwen Yang; Yumeng Qin; Wen Hao; Lin Cai; Mengmeng Guo; Guozhen Fang; Shuo Wang (Food Research International, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Efficient perovskite solar cells enabled by carborane-based interfacial grain boundary passivation - Mingxuan Cai; Shuo Ding; Zhuoyuan Kong; Fangzheng Ning; Jie Zhou; Zhengguo Xiao; Qiao Lin; Yongyin Kang; Chaoyu Xiang (Chemical Engineering Journal, 2026)

Active far-to-close perception via optimal fishbone-view estimation for robotic truss tomato harvesting - Hefei Luo; Liang Gong; Shuo Zhang; Cheng Luo; Ziye Zhang; Feifan Wu; Zongxiao Li; Yangtian Lin; Chengjin Qin; Chengliang Liu (Computers and Electronics in Agriculture, 2026)

Exploring the built environment impacts on urban heat exposure: An autoencoder-based approach for integrating multiple indicators - Lin Shen; Qianqian Liu; Wenzhong Zhang; Shuo Lu (Journal of Environmental Management, 2026)

Steric hindrance modulation in covalent triazine frameworks enables ultrahigh SO2 and SF6 capture - Xiaoyu Wang; Zhaosheng Fan; Lin Hu; Chang Liu; Xiaocui Xie; Xiaojuan Gu; Mingxuan Liu; Yixian Du; Xu Yan; Chen Chen; Xiongli Liu; Lin Li; et al. (Chemical Engineering Journal, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Plant–soil feedback persists beyond host death to shape density-dependent plant competition - Ching-Lin Huang; Joe Wan; Shuo Wei; Chia-Hao Chang-Yang; Po-Ju Ke (Plant and Soil, 2026)

Coupled numerical investigation on focused wave interaction with offshore jacket platform and response assessment - Hong Lin; Qi Fan; Shuo Zhang; Kaixin Liang; Alexander Moiseevich Uzdin; Longcheng Wei; Zixuan Lin; Lei Yang (Ocean Engineering, 2026)

Exploring antennal asymmetry in electrophysiological response, behavior, and olfactory gene expression in the diamondback moth, Plutella xylostella (lepidoptera: plutellidae) - Houjun Tian; Shuo Lin; Yueqin Zheng; Ruibin Xu; Yun Yu; Yong Chen; Hui Wei (Journal of Insect Physiology, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

DFT-guided design of molecularly imprinted sensor for fluorescence and visualization dual-mode oxytetracycline detection - Yan Liu; Lin Cai; Wen Hao; Yichuan Cao; Guozhen Fang; Shuo Wang (Food Chemistry, 2026)

Multi-level design of a chitosan-based membrane: from sisal fiber reinforcement to surface micropatterning and hybrid hap for enhanced bone regeneration - Shuo Tang; Rui Lin; Yuqing Wang; Xinyuan Feng; Fang Shi; Yupeng Guo; Shu Huang; Xiang Hu; Liuyun Jiang (Carbohydrate Polymers, 2026)

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

Synthesis of visible-light-responsive magnetic recyclable ternary photocatalyst g-C3N4/Bi2O3/Fe3O4 for heavy metal stabilization from municipal solid waste incineration fly ash - Quanming Ren; Zunchao Ren; Feng Lin; Qingsong Zhang; Shuo Feng; Fei Cheng (Journal of Environmental Chemical Engineering, 2026)

Piezo-photocatalysis with BaTiO3 nanorod arrays–Ag nanoparticle composites for the photodegradation of rhodamine B - Yen-Lun Chiu; Thi Nghi Nhan Nguyen; Hsin-Yu Chi; Heng-Jun Lin; Kao-Shuo Chang (Journal of Environmental Chemical Engineering, 2026)

Flame impingement to facilitate the stability of NH3-CH4 laminar diffusion flames: High-speed imaging and schlieren visualization - Yidu Tong; Chenyang Fan; Zheng Fu; Ye Liu; Huiyong Du; Bin Xu; Guorong Lin; Shuo Jin; Shuainan Yang; Mingliang Wei (Fuel, 2026)

Innovative approaches to carbon capture using fluidized bed reactors: A brief review - Yuanqiang Duan; Lin Li; Dennis Lu; Shuo Zhang; Guang Sun; Zhengkun Sun; Lunbo Duan (Fuel, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

Bandgap-engineered iron-coordinated quercetin for enhanced visible-light photodynamic inactivation and strawberry preservation - Kaiyuan Su; Haoqian Chen; Zhuoran Guo; Yikai Song; Lin Yang; Jun Liu; Jianlong Wang; Wentao Zhang; Shuo Shi (Food Bioscience, 2026)

Unraveling microplastic retention distribution in porous media: A unified framework coupling flow conditions and particle properties - Haiyu Yuan; Guangqiu Jin; Qihao Jiang; Shuo Wang; Hao Lin; Zhongtian Zhang; Xiangfei Qi; Hanqing Zhao (Environmental Pollution, 2026)

Multi-parameter full waveform inversion based on optimal transport distance in VTI media - Shuo Wei; Bingshou He; Mingqian Wang; Yuzhao Lin (Computational Geosciences, 2026)

Talarombrevisone A, an β -aminopropionate with two polyketide units, isolated from an endophytic fungus Talaromyces brevis - Yun-He Tuo; Zhong-Duo Yang; Jian-Guo Chen; Cui-Juan Xu; Lin-bo Liu; Tian-Kun Zhao; Yue Li; Li-Bin Xia; Shuai Yu; Ai-Hong Zhao; Shuo Li (Natural Product Research, 2026)

Multiple macroeconomic benefits from mixed coastal flooding adaptation in China's coastal cities - Jiaju Lin; Shuyu Yang; Shuo Wang; Yuning Zhao; Yanhong Lin; Xiongzhi Xue; Yurong Ouyang (Ocean & Coastal Management, 2026)

Optimal management of co-location marine activities in three-dimensional space: A Stackelberg game-based framework - Shuo Wang; Jiaju Lin; Chao Liu; Yanping Li; Saiya Xu (Ocean & Coastal Management, 2026)

InceptionFormer: A deep learning framework for UAV LiDAR point cloud completion to improve tree parameters estimation in dense forests - Binhan Luo; Jian Yang; Shuo Shi; Ruilin Gan; Zhongliang Wu; Sihao Wang; Ao Wang; Lin Du; Wei Gong (Remote Sensing of Environment, 2026)

Nature-inspired bicontinuous-topology 3D-printed TPMS solar interfacial evaporator - Yifeng Liao; Yizhe Liu; Lin Ren; Yujun Wei; Zhijian Huang; Jing Zhang; Zhongxin Xu; Jianing Wu; Junyang Tao; Shudong Yu; Shuo Wu (Chemical Engineering Journal, 2026)

Ytterbium/zinc hierarchically modulated aggregation-induced emission active metal-organic framework for ratiometric-electrochemiluminescence and fluorescence dual-mode detection of nitrofurazone - Wen Hao; Lin Cai; Guangrao Chen; Mengmeng Guo; Jie Wu; Guozhen Fang; Shuo Wang (Chemical Engineering Journal, 2026)

Antibiotic sensitivity as a key Determinant: B. Subtilis Reshapes the Microecology to mitigate antibiotic resistance genes during composting - Xiaoxia Hao; Lijia Jiang; Mengting Chen; Shuo Liu; Li Zhu; Dongmei Jiang; Lin Bai (Bioresource Technology, 2026)

Mechanisms of cold adaptation in a novel marine eukaryotic phytoplankton—psychrophilic microalga Chlamydomonas sp. LWD-1 - Di Zhang; Songlin Ma; Gerui Yin; Shuo Lin; Bailing Chen; Keqing Liu; Weidong Liu; Yiwen Chen; Baolin Jia; Zhanyou Chi; Fantao Kong (Plant Cell Reports, 2026)

Gut Microbiota Composition and Predicted Functional Profiles of Fishes Along an Urbanization Gradient in Shanghai’s Suzhou River, China - Shuo Feng; Hua Xue; Xirong Lin; Ana Wu; Wenqiao Tang (Fishes, 2026)
Ongoing urbanization continuously reshapes water quality, habitat structure, and biological communities in river ecosystems; however, its impacts on host-associated microbial communities remain poorly documented. The fish gut microbiota, a critical interface between the aquatic environment and host physiology, is widely recognized as an integrative indicator of both environmental change and host ecological traits. This study established a continuous urbanization gradient along Shanghai’s Suzhou River, spanning from suburban areas through the outer and inner ring roads to the city center. Five common wild fish species (Coilia nasus, Hemiculter bleekeri, Culter alburnus, Acheilognathus macropterus, and Pseudorasbora parva) were collected, and their gut microbiota were characterized via high-throughput 16S rRNA gene sequencing. Significant variation in OTU richness, alpha diversity, and community structure was observed across urbanization gradients and among fish species. Principal coordinate analysis revealed that samples from suburban areas were structurally distinct from those collected in other zones, whereas inner-ring and urban-core areas exhibited substantial compositional overlap. Taxonomic analysis revealed that Firmicutes and Pseudomonadota dominated all samples; however, their relative abundances and genus-level composition varied considerably among fish species and across the urbanization gradient. PICRUSt-based functional prediction indicated that metabolic pathways predominated, particularly those involved in global and overview maps, carbohydrate metabolism, amino acid metabolism, energy metabolism, and metabolism of cofactors and vitamins. Collectively, these findings demonstrate that fish gut microbial communities exhibit spatial structuring along the urbanization gradient, with species-specific responses linked to ecological traits. This study provides valuable data on host-associated microbial communities in urban rivers and offers a reference for incorporating microbial indicators into urban water ecological assessments.

The antifungal potential and mechanistic action of durian shell water extract against citrus pathogen Fusarium oxysporum - Haiyan Lin; Jingjing Shan; Yineng Wang; Yiliang Cai; Shuo Shan; Xianglong Chen; Wei Hong; Ruiyu Zhu (Food Microbiology, 2026)

Seismic performance of trussed concrete-filled steel tubular (CFST) hybrid structures: Experiments - Zhan-Shuo Liang; Lin-Hai Han; Ming Xiao (Engineering Structures, 2026)

Effect of perovskite A-site disorder on its activity in solid-state CO2 electrolysis - Shuo Liu; Lin-Bo Liu; Biao Ouyang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Jing-Li Luo; Subiao Liu (Chemical Engineering Journal, 2026)

In situ cultivation and chromogenic screening: a dual approach for rapid discovery of PDE1 inhibitors from pinus-tree associated microbes - Cui-Juan Xu; Shuo Li; Zhong-Duo Yang; Lin-Bo Liu; Yun-He Tuo; Yong-Jiao Niu; Lei-Lei Chen; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao (World Journal of Microbiology and Biotechnology, 2026)

Mechanisms of phosphorus release from coastal sediments driven by organic matter enrichment at high nitrogen concentrations - Chun-Pu Zhao; An-Hao Wang; Ying Zeng; Wen-Hao Yin; Cheng Luo; Shi-Xia Liu; Miao Liu; Hai-Jun Wang; Xiao-Wen Li; Ji-Lin Xu; Shuo-Nan Ma (Marine Pollution Bulletin, 2026)

Three-dimensional numerical investigation of vortex-induced motion of low aspect ratio cylinders - Jin Miao; Hongyuan Sun; Haihua Lin; Dexin Liu; Shuo Ren; Kefeng Yan; Jing Xu (Ocean Engineering, 2026)

Pyrimidine biosynthesis repression fuels cost and survival of trimethoprim/sulfamethoxazole – Resistant E. coli - Xiaoxia Hao; Guilin Zheng; Huanzhen Li; Shuo Liu; Li Zhu; Dongmei Jiang; Lin Bai (Journal of Hazardous Materials, 2026)

Corrigendum to “Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum” [Geochim. Cosmochim. Acta 411 (2025) 233–249] - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2026)

Smartphone-assisted portable colorimetric detection of Salmonella based on a dual signal amplification mediated nanozyme cascade aptasensor - Qing Kang; Chenjing Ma; Yidi Liu; Xin Yu; Tong Lin; Jingbo Jiao; Yukun Huang; Shuo Wang; Xinjun Du (Food Bioscience, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Membrane aerated biofilm reactor for largely enhanced nitrogen removal in low carbon/nitrogen ratio municipal wastewater: integrating nitrification, partial denitrification, and anammox - Xiwei Cao; Lin Zhang; Haoran Tu; Ting Li; Guofeng Wang; Ling Xiao; Yupeng Zhang; Peng Liu; Yi Li; Jiaye Li; Xinglin Li; Boyang Hu; et al. (Bioresource Technology, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Detection and tracking of a gauze sponge in minimally invasive surgery using a YOLO and R-CNN based model - Shuo-Lun Lai; Yung-Chien Chou; Chi-Sheng Chen; Tzu-Chia Tung; Been-Ren Lin; Ruey-Feng Chang (Medical & Biological Engineering & Computing, 2026)

Implications of phase information from GPS and GRACE(FO) for identifying GPS stations influenced by poroelastic deformation - Fei Lin; Yu Sun; Natthachet Tangdamrongsub; Shuo Zheng; Bao Zhang (Journal of Geodesy, 2026)

Monocyte-mediated mechanisms in idiopathic pulmonary fibrosis: opportunities for early intervention - Zhiguo Mao; Ying Liu; Chengfu Han; Xingyi Yang; Xiangke Lin; Shuo Tian; Mingsan Miao (Apoptosis, 2026)

Schisantherin A alleviates hepatotoxicity induced by diosbulbin B in mice via suppressing metabolic activation of diosbulbin B - Shuo Wang; Bufan Yang; Guangyao Li; Dongju Lin (Toxicology and Applied Pharmacology, 2026)

Formononetin protects against oxaliplatin-induced peripheral neurotoxicity via Nrf2/HO-1 antioxidant pathway without impairing anticancer efficacy - Yang-Chen Chang; Wan-Hsuan Lin; Horng-Huey Ko; Yi-Ching Lo; Hsun-Shuo Chang; Hui-Ching Lin; Yih-Fung Chen (NeuroToxicology, 2026)

Refining the parameterization of atmospheric particle settling velocity in seawater: Insights from interpretable machine learning - Shuo Wang; Huiwang Gao; Haoyu Jin; Xiaohong Yao; Yihua Lin (Journal of Hazardous Materials, 2026)

Differential accumulation of clenbuterol hydrochloride in vegetables under hydroponic exposure: Physiological responses and health risk analysis - Kai Wang; Shuo Zhang; Wanzhang Lin; Minling Gao; Weiwen Qiu; Youming Dong; Huaiying Yao; Zhengguo Song (Journal of Hazardous Materials, 2026)

Hydrothermal extraction and characterization of hemicellulose from biomass as a natural emulsifier - Yilin Li; Shuo Jiang; Zhiyuan Xu; Yixiang Xu; Seunghee Yoon; Xuanbo Liu; Yifan Cheng; Sean F. O'Keefe; Jactone Ogejo; Feng Lin; Yiming Feng; Haibo Huang (Food Chemistry, 2026)

Neurodevelopmental toxicity induced by iron oxide nanoparticles: Insights from chick and zebrafish embryonic models - Bi-Xia Huang; Tao Zhang; Qing-Bin Dong; Peng-Xing Lin; Yi Zhou; Xin-Shuo Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

The p -JNKThr183/Tyr185 / p -Keap1Thr43 /Keap1 axis mediates arsenic-induced endothelial dysfunction by coordinating Chaperone-mediated autophagy with macroautophagy - Jinyu Li; Jin Cheng; Zhihan Yang; Lin Gao; Qiaoling Liu; Jing He; Yishan Dong; Shuo Wang; Jing Cui; Ziqi Xu; Dianjun Sun; Wei Zhang (Chemico-Biological Interactions, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Enhanced El Niño–Southern Oscillation impact on Somali jet under greenhouse warming - Haodong Wang; Tao Geng; Wenju Cai; Shuo Wu; Xiaopei Lin (Climate Dynamics, 2026)

A 13C-PLFA approach to assess the crop carbon allocation efficiency and arbuscular mycorrhizal assimilation capacity under conservation tillage - Wen-Sheng Liu; Shuo Yao; Zhuo-Jun Lin; Olatunde Pelumi Oladele; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Biology and Fertility of Soils, 2026)

Intercropping maize and soybean promotes specialized soil microbial communities and boosts carbon and nitrogen cycling in a semi-arid agroecosystem - Olatunde Pelumi Oladele; Shuo Yao; Ming-Zhu Huang; Yu-Gang Tian; Xin Zhao; Yash Pal Dang; Wei Bai; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Dual activation of AhR and Nrf2 pathways by the natural stilbenoid tapinarof protects against particulate matter-induced skin barrier dysfunction - Chia-Hsuan Lin; Horng-Huey Ko; Jin-Ye Wu; Hsun-Shuo Chang; Chia-Hung Yen; Chien-Chih Chiu; Yih-Fung Chen (Toxicology and Applied Pharmacology, 2025)

Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2025)

Investigation of the structure-activity relationship of resveratrol and its glycosylated and acylated derivatives in relation to their α-glucosidase inhibitory activities - Changdong Lin; Juyuan Luo; Shuo Wang; Cheng Shen; Shucan Zhang; Zhibo Song; Yumei Ma; Yongling Liu; Yulin Li; Tao Chen (Food Chemistry, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Mechanical performance of an assembled 3D auxetic hybrid structure under eccentric and axial compression - Jia Shuo Liu; Yi Zhang; Xiang Jie Wei; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Tao Ding; Jia Hui Zhang; Lin Hua; Tong Cheng; Xin Ren (Engineering Structures, 2025)

Interaction between layered mantle flow and progressively thinned lithosphere beneath the Armenia Volcanic Highland: Evidence from seismic azimuthal anisotropy - Jing-Hui Tong; Tai-Lin Tseng; Pei-Ying Patty Lin; Khachatur Meliksetian; Shuo-Fen Chang; Bor-Shouh Huang; Elya Sahakyan; Mikayel Gevorgyan; Lilit Sargsyan (Earth and Planetary Science Letters, 2025)

Divergent environmental controls on branched tetraethers along precipitation gradients in soils of the Tibetan Plateau - Yanwu Duan; Yuling Zhou; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Lin Chen; Yuanxin Li; Mengjing Li; Xianyong Cao; Fahu Chen (Chemical Geology, 2025)

Inhibitory effect of carvacrol nanoemulsions on Staphylococcus aureus and its biofilms - Yifei Wang; Feng Chen; Zongxin Lu; Lin Ye; Xiaobo Yang; Josphat Njenga Gichure; Joanna Trafiałek; Shuo Zhang; Shoukui He (Journal of Consumer Protection and Food Safety, 2025)

Novel insights into quorum-sensing microbe combined with dimethylsulfoniopropionate enhancing bioremediation of oil-contaminated sediment under typical deep-sea conditions: The performances and molecular mechanisms - Shugang Hu; Shijie Li; Lingzhe Wang; Shuo Wang; Dongle Cheng; Jianliang Xue; Yu Gao; Siheng Lin; Chengbo Li; Yanlu Qiao; Yuyang Liu (Marine Pollution Bulletin, 2025)

How effective is marine spatial planning in managing transboundary nearshore seawater pollution? Quasi-experimental evidence from China - Shuo Wang; Yanhong Lin; Jiaju Lin; Xiongzhi Xue; Zhiwei Zhang (Ocean & Coastal Management, 2025)

Low-carbon investment volatility under policy uncertainty: Evidence from equity markets and implications for carbon capture deployment - Dapeng Lin; Yanfen Wang; Chang Wang; Wen Jiang; Liyuan Zhang; Shuo Hu; Kai Du; Chengdong Yuan (Journal of Cleaner Production, 2025)

Multi-scale quantitative analysis of grotto sandstone degradation considering inorganic salt phase transitions - Sicheng Lin; Luqi Wang; Wengang Zhang; Shuo Wang; Zihua Xiong; Siwei Jiang; Gang Zhao (International Journal of Rock Mechanics and Mining Sciences, 2025)

Peptidomics and molecular docking reveal digestion-resistant IgE-binding epitopes in bovine β-lactoglobulin and α-lactalbumin from simulated infant digestion - Fan Yang; Hongwei Zhang; Shaolei Wang; Xue Zhao; Yuying Tang; Jianhua Zeng; Weixue Zhao; Shuo Feng; Changhong Ma; Lanwei Zhang; Kai Lin (Food Chemistry, 2025)

Acidification boosts the photodynamic activity of anthocyanidin for enhanced sterilization - Zhenqing Guo; Yajie Wang; Xinqi Wang; Ting Du; Kaiyuan Su; Lin Yang; Yaru Han; Shuo Shi; Jianlong Wang; Wentao Zhang (Chemical Engineering Journal, 2025)

Monocyte/macrophage-mediated transport and intratumoral bacteria-responsive ZIF nanoplatform for enhanced immunotherapy against microsatellite-stable colorectal cancer - Xietao Ye; Yeyang Sun; Lin Yang; Chen Chen; Shihao Li; Shuo Dong; Xiaoying Qin; Xiaoqi Li; Congyan Liu; Jiege Huo; Yuping Liu; Yan Chen (Chemical Engineering Journal, 2025)

Two pairs of isomeric resin glycosides from Argyreia obtusifolia - Shuo Chen; Yi-Lin Niu; Zhi-Tong Li; Hong-Hua Cui; Yong-Qin Yin; Yan-Fen Chen (Phytochemistry Letters, 2025)

Effect of 7-O-glycosyl acylation of flavonoids from barley seedlings on α-glucosidase inhibition - Tao Chen; Changdong Lin; Weihang Lu; Shuo Wang; Cheng Shen; Juyuan Luo; Yulin Li (Food Chemistry, 2025)

Origin-dependent quality traits of Stropharia rugosoannulata: A comprehensive analysis of nutritional, aroma, and taste biomarkers - Yue Geng; Songyi Lin; Ruixue Wang; Liren Zhao; Shuo Xu; Dong Chen (Food Bioscience, 2025)

Cluster-net structured polymer hydrogel elastomer engineered as artificial temporomandibular joint disc for establishing mechanical homeostasis - Hao Dai; Jianming Zhao; Kun Qiao; Tianyi Lin; Yajie Xie; Lin Lan; Jie Wang; Yuchen Liu; Shuo Chen; Yudong Zheng; Yang He (Chemical Engineering Journal, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Spatial–Temporal Dynamics of Drought Characteristics and Its Influencing Factors on Tibetan Plateau - Zhizhu Zhou; Wenjun Yu; Lin Zhao; Yanzhong Li; Shuo Cheng; Jiazhe Duan; Yincong Xing; Wei Shao (International Journal of Climatology, 2025)
Assessing drought on the Tibetan Plateau (TP) is essential for understanding the spatial characteristics of the region's hydrological regimes, as well as the trends of the evolving climate‐ecological system. Based on the precipitation and the potential evapotranspiration data from the ERA5‐Land dataset, this study evaluated the drought characteristics on the TP from 1950 to 2022 using the Standardised Precipitation Evapotranspiration Index (SPEI) and the Run theory. The analysis of SPEI at multiple time scales—SPEI‐1 (monthly), SPEI‐3 (seasonal), and SPEI‐12 (annual)—consistently revealed a pronounced drying trend across the TP over the past 70 years. Notably, the wet‐to‐dry transition points were detected in 2000 and 2001 based on the SPEI‐1 and SPEI‐3 series, respectively, while the SPEI‐12 series indicated a later shift occurring in 2004. In addition, the SPEI values indicated a spatial trend of increasingly severe drought conditions from south to north. Particularly, pronounced drought stress was observed in the Brahmaputra, Ganges, and Indus basins, as well as in the southern regions of the Inner Plateau. Furthermore, the relationships between drought variability and key climatic drivers—including sunspots, El Niño‐Southern Oscillation (ENSO), temperature (TEMP), and annual mean areal precipitation (AP)—were identified through cross‐wavelet transform (XWT) and wavelet coherence analysis (WTC). In general, the analysis showed that the SPEI values on the TP were negatively correlated to ENSO and TEMP but positively correlated to sunspots and AP. This study offers a comprehensive spatiotemporal assessment of drought dynamics across the TP, providing critical insights for regional water resource management and climate change adaptation planning.

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Impacts on structure, lipase-inhibitory activity, and digestive characters of fermented coconut protein with Lactobacillus strains - Yufang Tian; Tao Lin; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Elham Azarpazhooh; Marjan Ajami; Ghahvechi Chaeipeima Masha; Xin Rui; Wei Li (Food Bioscience, 2025)

Standard strategy for developing multicomponent nanopesticides: From gene function analysis to co-delivery nano-platform construction - Qinhong Jiang; Min Dong; Lin Che; Che Li; Xian Zhang; Meizhen Yin; Jie Shen; Shuo Yan (Chemical Engineering Journal, 2025)

Perovskite-socketed FeCoNiCu quaternary alloy nanoparticles for efficient CO2 reduction in solid oxide electrolyzer - Shuo Liu; Lin-Bo Liu; Ming Yang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Artificial neural network-based ground motion prediction equations for Sichuan-Yunnan area of China - Jianwen Cui; Dawei Lu; Shuo Xu; Guoliang Lin; Yahong Shen; Zhihao Cui (Acta Geophysica, 2025)
This study presents a novel ground motion prediction equation (GMPE) for the Sichuan-Yunnan region of China based on artificial neural networks (ANNs). Utilizing data from 207 earthquake events and 3537 ground motion recordings collected since 2007, the ANN-based GMPEs predict peak ground acceleration (PGA) and pseudo-spectral acceleration (PSA) for periods ranging from 0.04 to 6.0 s. The model incorporates five key parameters: magnitude, epicentral distance, site conditions (represented by the predominant period $${T}_{0}$$ T 0 derived from horizontal-to-vertical spectral ratios HVSR), hypocentral depth, and styles of faulting. A weighted loss function is employed during ANN training to address data imbalances, particularly the scarcity of near-field recordings. Residual analyses indicate that both inter-event and intra-event variabilities fall within acceptable limits. Comparisons with observed ground motions and existing GMPE commonly used in China confirm that the proposed ANN-based GMPE effectively captures key ground motion characteristics.

Cerebral network topology and peak width of skeletonized mean diffusivity changes associated with cognitive impairment in patients with obstructive sleep apnea - Xiaoshan Lin; Shiwei Lin; Fajian Wei; Shengli Chen; Qunjun Liang; Shuo Li; Yingwei Qiu (Brain Imaging and Behavior, 2025)

Comparative fitness of Proprioseiopsis asetus (Acari: Phytoseiidae) as a biocontrol agent against Megalurothrips usitatus and Thrips flavus - Hui Zhang; Li Sun; Shuo Lin; Yuxian He; Hui Wei; Xia Chen (Experimental and Applied Acarology, 2025)

Dual-stage matrix elimination-ICP-MS methodology for REEs profiling in barite-associated ores - Xue-lin Dong; Jun-han Liu; Zheng-xun Jia; Shao-zhan Tang; Shuo-yun Tong; Yu-xiang Xiong; Lei Ouyang (Analytica Chimica Acta, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Sous-vide cooking as a promising approach for developing high-quality salt pan shrimp products - Chenqi Li; Songyi Lin; Tingjia Chen; Shuo Wang; Xixin Qian; Dong Chen; Ruming Wang; Na Sun (Food Chemistry, 2025)

Performance of trussed concrete-filled steel tubular (CFST) hybrid structures subjected to eccentric compression - Zhan-Shuo Liang; Lin-Hai Han (Engineering Structures, 2025)

Assessment of the rat acute oral toxicity of quinoline-based pharmaceutical scaffold molecules using QSTR, q-RASTR and machine learning methods - Jianing Xu; Ting Ren; Feifan Li; Shuo Chen; Tengjiao Fan; Lijiao Zhao; Rugang Zhong; Guohui Sun; Ning Lin (Molecular Diversity, 2025)

Demulsification characteristics of electrostatic–swirling coupling enhanced migration - Guidong Chen; Silong Feng; Shuo Liu; Lin Li; Xiangyi Long; Qiang Yang; Hao Lu (Journal of Water Process Engineering, 2025)

From soft to hard adventure: Examining experienced mountaineers’ mountaineering intentions through the lens of the theory of planned behavior - Shih-Shuo Yeh; Tai-Ying Chiang; Kuan-Ying Chen; Chen-Lin Lee; Tzung-Cheng Huan (Journal of Outdoor Recreation and Tourism, 2025)

Microwave heating as a promising alternative to traditional two-stage heating in the production of sodium-reduced shrimp surimi - Xixin Qian; Songyi Lin; Shuang Li; Shuo Wang; Chenqi Li; Dong Chen; Na Sun (Innovative Food Science & Emerging Technologies, 2025)

Adsorption and oxidation of NO and N2O on soot surfaces: Evolution of functional groups - Shuo Jin; Chenyang Fan; Zheng Fu; Haizhao Li; Ye Liu; Bin Xu; Huiyong Du; Guorong Lin; Mingliang Wei (Fuel, 2025)

A molecularly imprinted near-infrared electrochemiluminescence sensor based on copper nanowires and signal dual-amplification strategy for the sensitive detection of enrofloxacin - Jie Wu; Ling Wu; Mengmeng Guo; Wen Hao; Lin Cai; Guozhen Fang; Shuo Wang (Food Chemistry, 2025)

The shrimp NF-κB pathway is activated to mediate the antioxidant defense and apoptosis under ammonia-N stress - Hongbiao Zhuo; Lanting Lin; Yuan Zhang; Shuo Fu; Jinyan Li; Xiaoxun Zhou; Guangbo Wu; Chaoan Guo; Jianyong Liu (Fish & Shellfish Immunology, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Stability and Adaptability of Sugar Beet Examined Based on AMMI and BLUP–GGE Biplot Analyses - Yuhang Lin; Xinwang Dang; Xiaohang Hu; Yanli Li; Shuo Liu (Sugar Tech, 2025)

High-pressure Raman spectroscopy of Al-rich and pure-Mg phase D - Chaowen Xu; Li Zhang; Xiaofeng Lu; Yanhao Lin; Shuo Qu; Shuchang Gao; Fengxia Sun; Ying Li (Physics and Chemistry of Minerals, 2025)

Molecular docking and molecular dynamics simulations revealed interaction mechanism of acetylcholinesterase with organophosphorus pesticides and their alternatives - Jiawen Yang; Lin Chen; Shuo Wang; Bing Zhao; Ruige Wang (Archives of Toxicology, 2025)

From non-affinity to high-affinity: Rapid preparation of nanobodies utilizing high-precision alphafold and structural-interaction analysis for detection of enrofloxacin in marine fish - Guoqiang Li; Chang Liu; Shuo Qiu; Lin Wei; Limin Cao; Kaiqiang Wang; Xiudan Wang; Hong Lin; Jianxin Sui (Journal of Hazardous Materials, 2025)

Experimental and Numerical Investigation on Mechanical Properties of Large-Diameter Metallurgically Clad Pipes - Feng Wang; Yanan Gao; Zhiguo Hu; Shuo Yang; Zhenying Cui; Rui Fu; Lin Yuan (Journal of Marine Science and Engineering, 2025)
Bimetallic-clad pipes demonstrate exceptional advantages in transporting corrosive oil and gas through the combination of the load-carrying capacity of the base material and the anti-corrosive function of the thin layer of corrosion-resistant alloy. This study investigates the mechanical properties of 24-inch X65 + Alloy625 metallurgically clad pipes through experimental tests and finite element analysis. Uniaxial tensile testing with digital image correlation reveals uniform deformation between the base and clad layers until interfacial failure initiates at an average strain threshold of 34.17%. Microstructural characterization shows continuous metallurgical bonding, with the X65 layer exhibiting polygonal ferrite and bainitic phases, contrasting with the austenitic equiaxed grain structure of Alloy625. In terms of numerical modeling, finite element analyses that consider both initial geometric imperfections and manufacturing-induced residual stresses are performed to evaluate the bending response of the clad pipe. The effect of initial ovality and residual stresses on its bending capacity is also studied.

Experimental and simulation study on the formation and microstructure of ionic liquid microemulsion collectors used for low-rank coal slime - Meng He; Lixin Song; Shuo Yang; Feifei Wang; Gang Hu; Liqing Sun; Lin Li; Xiaofang You (Fuel, 2025)

Natural phenolic Acid-Functionalized polyurethane microcapsules with superior foliar retention and UV protection for improving pesticide efficacy and safety - Yanan Xiao; Mengdie Li; Shuhui Hu; Lin-Lin Yang; Jian Wang; Chang Yan; Yi Tong; Shuo Liu; Liqian Cao; Wenneng Wu; Bo Zhang (Chemical Engineering Journal, 2025)

PLATZ transcription factors and their emerging roles in plant responses to environmental stresses - Hongxia Zhang; Lu Liu; Zhenzhen Li; Shuo Wang; Li Huang; Sue Lin (Plant Science, 2025)

Experimental and numerical analysis on two-way hull–propeller coupled effect of a fully-actuated AUV - Tian Xia; Shuo Liu; Tao Wang; Jiangyang Li; Wanglin Lin; Bingbing Zhang; Yong Cai; Wen Xu (Ocean Engineering, 2025)

Establishing age-group specific reference intervals of human salivary proteome and its preliminary application for epilepsy diagnosis - Nianci Xue; Xia Xia; Yini Wang; Xianju Li; Nairen Zheng; Yi Wang; Baoying Gong; Bin Zhang; Yanjia Chen; Yue Chen; Yanjuan Li; Hong Cao; et al. (Science China Life Sciences, 2025)

Two new species of the extinct subfamily Alitrepaninae (Coleoptera: Bostrichidae) from the Upper Cretaceous (Cenomanian) Kachin amber in northern Myanmar - Huan Wang; Yuan Peng; Qianhui Lin; Ruiqing Tao; Zirui Zhang; Shuo Wang (Cretaceous Research, 2025)

Dissolved organic carbon can alter coastal sediment phosphorus dynamic: Effects of different carbon forms and concentrations - Shuo-Nan Ma; Xu-Meng Dong; Ji-Lin Xu; Chun-Pu Zhao; Miao Liu; Hai-Jun Wang; Erik Jeppesen (Chemosphere, 2025)

Numerical study on hydrodynamic characteristics, wave forces and dynamic responses of offshore jacket platform under tsunami-like solitary waves - Hong Lin; Shuo Zhang; Alexander Moiseevish Uzdin; Longcheng Wei; Qi Fan; Lei Yang (Ocean Engineering, 2025)

Emission characteristics of biogenic volatile organic compounds in a subtropical pristine forest of southern China - Xi Chen; Daocheng Gong; Youjing Lin; Qiao Xu; Yujin Wang; Shiwei Liu; Qinqin Li; Fangyuan Ma; Jiangyong Li; Shuo Deng; Hao Wang; Boguang Wang (Journal of Environmental Sciences, 2025)

Decoding the textural deterioration of ready-to-eat shrimp: Insights from dynamic myofibrillar protein changes during thermal sterilization - Shuo Wang; Songyi Lin; Shuang Li; Xixin Qian; Chenqi Li; Na Sun (Food Research International, 2025)

Built-in potential-regulated and exogenous excited electrochemiluminescence sensor based on dual-monomers molecularly imprinted polymer for the biomimetic detection of thiabendazole - Wen Hao; Jingwen He; Jie Wu; Lin Cai; Yifei Wang; Guozhen Fang; Shuo Wang (Food Chemistry, 2025)

Performance and calculation of trussed concrete-filled steel tubular (CFST) hybrid structures subjected to bending - Zhan-Shuo Liang; Lin-Hai Han; Pu Wang (Engineering Structures, 2025)

Near-infrared electrochemiluminescence/smart visual dual-channel sensor based on magnetic derivative and microchip of terbium-based double-ligand MOG for detecting nitrofurazone and Cr(VI) - Lin Cai; Wen hao; Yichuan Cao; Jie Wu; Yan Liu; Guozhen Fang; Shuo Wang (Chemical Engineering Journal, 2025)

In-situ trichosanthin-IL2/pectin dynamic hydrogel activates dendritic cells and reverses T cell exhaustion for post-operative cancer therapy - Zeyun Gu; Guihua Chen; Nan Gao; Shuo Yao; Xiaoru Zhang; Quangang Xu; Wei Xiong; Lin Liu; Qin Liu; Dan Yin; Xiao-Ming Zhu; Yongzhuo Huang (Chemical Engineering Journal, 2025)

Freeze-dried cellulose-based aerogel with unidirectional pore structure for anionic dyes and oils adsorption - Shuo Zhang; Yanqiu Pan; Qi Fan; Wei Wang; Runze Lin (Chemical Engineering Journal, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Heavy metal removal and recovery from contaminated sediments based on bioelectrochemical systems: Insights, progress, and perspectives - Shu-Hui Liu; Jin-Shuo Liu; Chi-Wen Lin (International Biodeterioration & Biodegradation, 2025)

Integration of cobalt coordination polymer-based triboelectric nanogenerators as sustainable power sources for self-driven selective photocatalytic reactions - Fei Wang; Ying-Ying Zhang; Shuo Li; Lin Zhang; Yuanmeng Tao; Jiaxing Cui; Dandan Wang; Mingli Jiao; Chao Huang (Chemical Engineering Journal, 2025)

Parameter Identification of an Unmanned Sailboat Combining Experiments and Numerical Analysis - Yifan Chen; Shuo Liu; Tian Xie; Zhaozhao Zhang; Yu Zhang; Wanglin Lin; Kaiyou Jiang; Tao Wang (Journal of Marine Science and Engineering, 2024)
It is meaningful to develop an accurate model to predict the dynamical motion of an unmanned sailboat. Considering cost and convenience, this work proposes a parameter identification method based on the combination of experiments and numerical analysis. Firstly, a free-running trial is carried out by utilizing the propellers on the studied sailboat to acquire real navigation information. Secondly, particle swarm optimization (PSO), which is highly efficient and easily implemented, is designed to acquire the hydrodynamic parameters of the sailboat’s hull. At the same time, the aerodynamic parameters of the sail are acquired by computational fluid dynamics (CFD) simulation. Finally, a three degree-of-freedom (DOF) model is established, the effectiveness of which is verified through comparisons between sea trials and simulation. The results prove that this parameter identification method has the desired accuracy and reliability.

In-situ online investigation of biogenic volatile organic compounds emissions from tropical rainforests in Hainan, China - Xi Chen; Daocheng Gong; Shiwei Liu; Xinxin Meng; Zhu Li; Youjing Lin; Qinqin Li; Ruiyun Xu; Sijun Chen; Qinghua Chang; Fangyuan Ma; Xiaoxiao Ding; et al. (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Cross-Scale Quantitative and Qualitative Study of Grotto Sandstone Under Salt Weathering - Sicheng Lin; Luqi Wang; Wengang Zhang; Shuo Wang; Kaiqiang Zhang; Yu Lei; Siwei Jiang; Huili Chen; Gang Zhao; Xuemei Feng (Rock Mechanics and Rock Engineering, 2024)

The inequality of economic development increases the direct economic loss of storm surge disaster in China - Jiaju Lin; Shuo Wang; Yuning Zhao; Xiongzhi Xue (Ocean & Coastal Management, 2024)

Ameliorative effect of Schisandrol B against Diosbulbin B-induced hepatotoxicity via inhibiting CYP3A4-mediated bioactivation - Dongju Lin; Shuo Wang; Bufan Yang; Guangyao Li (Toxicology and Applied Pharmacology, 2024)

Evaluation of the texture characteristics and taste of shrimp surimi with partial replacement of NaCl by non‑sodium metal salts - Xixin Qian; Songyi Lin; Tingjia Chen; Shuang Li; Shuo Wang; Chenqi Li; Ruming Wang; Na Sun (Food Chemistry, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

CoFe-LDHs were grown on Co-layered hydroxides to achieve 3D-hierarchical flower like architecture for efficient oxygen evolution reaction - Shuo Liu; Yufan Zhang; Lin Hao; Anaclet Nsabimana; Shigang Shen (Journal of Environmental Chemical Engineering, 2024)

κ-Carrageenan improves the gelation capacity of Antarctic krill myofibrillar proteins through covalent and noncovalent interactions - Shuang Li; Songyi Lin; Pengfei Jiang; Xixin Qian; Shuo Wang; Na Sun (Food Hydrocolloids, 2024)

A novel vanadium-copper rechargeable battery for solar energy conversion and storage - Chunkun Lin; Jiangxin Wang; Kaixin Zhang; Huibin Shi; Yibing Liu; Kuanhong Mei; Minmin Liu; Yu Zhang; Shuo Li (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

The effects of dietary supplementation of ginseng stem and leaf saponins on the antioxidant capacity, immune response, and disease resistance of crucian carp, Carassius auratus - Ying-da Wang; Xin Meng; Yong-chao Guan; Ze-lin Zhao; Luo-tao Tao; Jin-shuo Gong; Xin-lan Liu; Yan Zhao; Xiao-feng Shan (Fish Physiology and Biochemistry, 2024)

Fish Stock Status and Its Clues on Stocking: A Case Study of Acanthopagrus schlegelii from Zhanjiang Coastal Waters, China - Hagai Nsobi Lauden; Xinwen Xu; Shaoliang Lyu; Alma Alfatat; Kun Lin; Shuo Zhang; Ning Chen; Xuefeng Wang (Fishes, 2024)
Global fisheries face overfishing challenges, endangering fish stock and biodiversity. While hatchery release stocking programs aim to bolster fish populations, their effectiveness remains uncertain due to challenges in data acquisition, such as obtaining stocking details and differentiating between wild and stocked individuals. This study evaluates the stock status of black sea bream (Acanthopagrus schlegelii) released in Chinese hatchery programs since the 1980s. Samples from Zhanjiang fish markets (January 2019–October 2021) underwent analysis using the length–weight relationship (LWR), length-based spawning potential ratio (LBSPR), and length-based Bayesian (LBB) methods. The male and female LWRs were W = 0.0188L2.9725 and W = 0.016L3.0284, respectively, and the observed condition factors indicated good health. The estimates imply that the region is conducive to species survival and can sustain its stocking programs. The LBSPR (SPR = 0.21 (0.17–0.25)) and LBB (B/BMSY = 1.1 (0.718–1.34), B/B0 = 0.37 (0.253–0.473)) results suggest a rebuilding population capable of replenishing to more sustainable levels. However, F/M and net selectivity estimates indicate that fishing practices target juvenile fish, limiting the reproductive potential of A. schlegelii. These findings underline the need for enhanced management strategies, including delayed harvesting and the use of size-specific fishing gear, to ensure the long-term sustainability of the species.

Ferrum effect on pyrolysis of IL swelling modified coal: Experiment and simulation - Zhihao Li; Beiji Yang; Shuo Yang; Feifei Wang; Qingbiao Wang; Lin Li; Xiaofang You (Minerals Engineering, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Construction of Covalent organic frameworks with bex topology for efficient photocatalytic hydrogen production - Lin Wang; Changzhi Han; Jingwen Pan; Shuo Li; Jia-Xing Jiang; Fengyun Guo; Shiyong Gao; Dongbo Wang; Yong Zhang (Chemical Engineering Journal, 2024)

Enhancement of beneficial microbiomes in plant–soil continuums through organic fertilization: Insights into the composition and multifunctionality - Wen-Jing Li; Xin-Yuan Zhou; Xin-Li An; Li-Juan Li; Chen-Shuo Lin; Hua Li; Hong-Zhe Li (Soil Ecology Letters, 2024)

Research on Hydrodynamics of Trans-Media Vehicles Considering Underwater Time-Varying Attitudes - Shuo Liu; Chihao Du; Yijie Han; Yu Zhang; Wanglin Lin; Yong Cai; Tao Wang (Journal of Marine Science and Engineering, 2024)
A trans-media vehicle is a new type of equipment that can adapt to two environments, water and air, to maintain optimal hydrodynamic and aerodynamic performance. However, no matter what kind of trans-media vehicle, its dynamics are much more complicated when traversing the interface of the medium, as the parameters are time-varying due to the change in ambient medium and vehicle attitudes. In order to improve the stability and performance of the trans-media vehicle in complex environments, an accurate mathematical model is established to characterize the dynamics of the trans-media vehicle in this process in this study. The time-varying hydrodynamic coefficients with different attitudes or depths are obtained using computational fluid dynamics software. The mathematical model is solved iteratively using a Runge–Kutta solver to calculate the dynamic response. A prototype of trans-media vehicle is fabricated, and motion experiments are performed in the pool. The experimental results confirm the effectiveness of the established model and lay the foundation for further controller design, providing a reference for the dynamic modeling of other similar equipment operating in complex environments. The primary novelty of this study lies in the fact that the established dynamic model considers the complex interaction between the attitude of the trans-media vehicle and the inherent different properties of water and air and utilizes computational fluid dynamics software to accurately obtain time-varying coefficients under different attitudes and depths. This approach not only recognizes the criticality of orientation-dependent hydrodynamic coefficients but also incorporates their temporal variations, which were often overlooked in previous studies.

Autistic traits and eating behaviors in Chinese preschoolers: Role of sensory profiles and home environment - Xiaocui Chen; Lifang Lin; Huiyun Xia; Shuo Zhao (Appetite, 2024)

Water scarcity footprint and water saving potential for large-scale green hydrogen generation: Evidence from coal-to-hydrogen substitution in China - Lifeng Du; Yanmei Yang; Xue Bai; Shuo Xu; Ling Lin; Min Liu (Science of The Total Environment, 2024)

Effects of different thermal sterilization conditions on the quality of ready-to-eat shrimp based on specific sterilization intensity - Shuo Wang; Songyi Lin; Shuang Li; Xixin Qian; Chenqi Li; Na Sun (Food Chemistry, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

Positive feedback between the negative phase of interannual component of the Pacific Decadal Oscillation and La Niña - Hong-Shuo Tang; Yu Zhang; Yu Kosaka; Jun-Chao Yang; Qi Shu; Yi Liu; Xiaopei Lin (Climate Dynamics, 2024)

Nanoplastic pollution changes the intestinal microbiome but not the morphology or behavior of a freshwater turtle - Shuo Gao; Shufang Zhang; Jiahui Sun; Xinni He; Shaoshuai Xue; Wenyi Zhang; Peng Li; Longhui Lin; Yanfu Qu; Georgia Ward-Fear; Lian Chen; Hong Li (Science of The Total Environment, 2024)

Arbuscular mycorrhizal fungi reduce soil N2O emissions by altering root traits and soil denitrifier community composition - Tangqing He; Wei Lin; Shuo Yang; Jiaqi Du; Bhoopander Giri; Cheng Feng; Frank S. Gilliam; Fuliang Zhang; Xiaoquan Zhang; Xuelin Zhang (Science of The Total Environment, 2024)

Predicting post-fire forest recovery using the 3-PG model with bi-temporal Landsat imagery in high-severity burned areas of Great Xing’an Mountain - Simei Lin; Linyuan Li; Shangbo Liu; Shuo Yang; Danyang Lin; Xun Zhao; Ling Chen; Huaguo Huang (Forest Ecology and Management, 2024)

Enhanced antibacterial activity of bovine milk exosome-based drug formulation against bacterial pathogens - Qingjun Xu; Shuo Yang; Kai Zhang; Ying Liu; Lin Li; Shaoqi Qu (Food Chemistry, 2024)

Impacts of mixed ferrous sulfate-biochar additives on humification and bacterial community during electric field-assisted aerobic composting - Kunhong Jiang; Dongmei Jiang; Shuo Li; Zhenzhen Guo; Liangbin Zhao; Jie Wang; Xiaoxia Hao; Lin Bai; Shixiu Qiu; Bo Kang (Bioresource Technology, 2024)

Synthesis of stable mesoporous Zr-MOFs using pyrazine-containing ligand for efficient capture of Pb(II) in wastewater - Lixiang Liu; Laidi Wu; Yue Chen; Yongfei Ma; Li Lin; Shuo Li; Xiujuan Yang; Hui Chen; Guojian Duan (Journal of Environmental Chemical Engineering, 2024)

Carbon-dots encapsulated luminescent metal–organic frameworks@surface molecularly imprinted polymer: A facile fluorescent probe for the determination of chloramphenicol - Mingfei Pan; Jiaqing Sun; Yixin Wang; Jingying Yang; Zhijuan Wang; Lin Li; Shuo Wang (Food Chemistry, 2024)

Phosphine oxide balanced charge transfer hybridization in multi-resonance emitters: towards ∼40% external quantum efficiency and preserved color purity - Su Chen; Yidan Wang; Jincheng Lin; Rundong Tian; Shuang Li; Yi Man; Shuo Chen; Jing Zhang; Chunbo Duan; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

Preparation of an injectable and photocurable carboxymethyl cellulose/hydroxyapatite composite and its application in cranial regeneration - He Qiu; Jing Wang; Hong Hu; Lu Song; Zhanhong Liu; Yang Xu; Shuo Liu; Xiangdong Zhu; Hang Wang; Chongyun Bao; Hai Lin (Carbohydrate Polymers, 2024)

Phosphorothioate-modified G-quadruplex as a signal-on dual-mode reporter for CRISPR/Cas12a-based portable detection of environmental pollutants - Kai Shi; Yi Tian; Sujun Liu; Wenjie Luo; Keer Liu; Lin Zhang; Ying Zhang; Jiali Chang; Jiaheng Zhang; Shuo Wang (Analytica Chimica Acta, 2024)

IFITM1 and IFITM2 inhibit the replication of senecavirus A by positive feedback with RIG-I signaling pathway - Huizi Li; Ming Chen; Tingting Zheng; Xiaoling Lei; Cunhao Lin; Shuo Li; Jiacong Mo; Zhangyong Ning (Veterinary Microbiology, 2024)

Atmospheric CO2 in the megacity Hangzhou, China: Urban-suburban differences, sources and impact factors - Yuanyuan Chen; Yanran Lu; Bing Qi; Qianli Ma; Kunpeng Zang; Yi Lin; Shuo Liu; Fengmei Pan; Shan Li; Peng Guo; Lihan Chen; Wengang Lan; et al. (Science of The Total Environment, 2024)

Dual-source signal amplification electrochemiluminescence sensor combined with molecularly imprinted polymers for the imidacloprid detection - Lin Cai; Yichuan Cao; Wen Hao; Haiyang Wang; Yifei Wang; Guozhen Fang; Shuo Wang (Science of The Total Environment, 2024)

Dynamic response and performance assessment of subsea sandwich pipelines with different interlayer subjected to underwater explosion - Hong Lin; Hao Xu; Lei Yang; Pingping Han; Shuo Zhang; Longcheng Wei; Guoming Chen (Process Safety and Environmental Protection, 2024)

A CFD-FEA coupled model for simulating dynamic response of offshore jacket platform under earthquake considering wind, wave, current and aftershock loads - Hong Lin; Haochen Luan; Alexander Moiseevish Uzdin; Shuo Zhang; Longcheng Wei; Lei Yang (Ocean Engineering, 2024)

A CRISPR/Cas12a-assisted bacteria quantification platform combined with magnetic covalent organic frameworks and hybridization chain reaction - Xuening Shi; Hang Li; Shuo Yao; Yukun Ding; Xiuzhu Lin; Hui Xu; Yi Liu; Chao Zhao; Tong Zhang; Juan Wang (Food Chemistry, 2024)

Bio-based and fireproof radiative cooling aerogel film: Achieving higher sustainability and safety - Wei Cai; Bicheng Lin; Liangyuan Qi; Tianyang Cui; Zhaoxin Li; Junling Wang; Sicheng Li; Chengfei Cao; Mohammad Ziaur Rahman; Xin Hu; Rujun Yu; Shuo Shi; et al. (Chemical Engineering Journal, 2024)

An Hsp70 promoter–based mouse for heat shock–induced gene modulation - Hangang Chen; Yangli Xie; Mei Zhang; Junlan Huang; Wanling Jiang; Ruobin Zhang; Can Li; Xiaolan Du; Hua Chen; Qiang Nie; Sen Liang; Qiaoyan Tan; et al. (Journal of Molecular Medicine, 2024)

Ascertaining sensitive exposure biomarkers of various metal(loid)s to embryo implantation - Mengyuan Ren; Tianxiang Wu; Shuo Yang; Ning Gao; Changxin Lan; Han Zhang; Weinan Lin; Shu Su; Lailai Yan; Lili Zhuang; Qun Lu; Jia Xu; et al. (Environmental Pollution, 2024)

Regulating framework aluminum location towards boosted light olefins generation in ex-situ catalytic pyrolysis of low-density polyethylene - Ting Wang; Xiang Feng; Dong Lin; Yan Li; Jingyuan Shang; Jinqing Zhang; Shuo Li; Yibin Liu; Hui Zhao; Zhe Ma; Xiaobo Chen; Xingong Zhang; et al. (Chemical Engineering Journal, 2024)

Uptrend of the Western North Pacific Tropical Cyclone Outflow Height during 1959–2021 - Yuan Sun; Zhihao Feng; Wei Zhong; Panmao Zhai; Yanluan Lin; Shuo Lyu (Journal of Meteorological Research, 2024)

Benefits and approaches of incorporating land–sea interactions into coastal spatial planning: evidence from Xiamen, China - Shuo Wang; Jiaju Lin; Xiongzhi Xue; Yanhong Lin (Frontiers in Marine Science, 2024)
As the land–sea interface, the coastal zone has become an increasingly key life-support system. However, it is also highly threatened by exposure to both ocean- and land-based human activities. The interdependencies of the land and sea systems require the integration of land and sea spatial planning to achieve sustainable development of coastal zones. There are different forms of land–sea spatial management integration globally. Whether a form can positively impact and how different institutional settings affect outcomes need further explanation. Therefore, this study explores the reasons for China’s planning integration through institutional reform by using the Graph Model for Conflicts Resolution and establishes a quantitative contradiction assessment method to examine whether this top-down institutional approach has played a role at the urban level. The results show that the planning of Xiamen city after reform has a lower total contradiction value, grid cell average and cell maximum value. This progress is made possible by unifying the land–sea spatial planning departments. The equilibrium solution of the Graph Model for Conflicts Resolution indicates that due to the different preferences of the land–sea management departments and the central-local governments, it is challenging to implement the Land–sea Coordination policy under separate land–sea management. By integrating land–sea management departments, deep-seated sectoral interests between horizontal departments do not remain. The impacts on integrated management of divergences in preferences of different vertical governments can be reduced. The research results provide a universal method for the contradiction evaluation and a management reference for other regions that want to integrate land–sea coordination into urban spatial planning.

Nickel-doped microtubular CeVO4 inspired by wood powder structure for visible light photocatalytic degradation of methylene blue and bacterial inactivation - Chang Ma; Bin Yin; Ying Zhang; Junfeng Chen; Shuo Zhang; Zuopeng Lin; Xing Gao; Minghui Guo (Journal of Water Process Engineering, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

Trussed concrete-filled steel tubular hybrid structures subjected to axial compression: Performance and design calculation - Zhan-Shuo Liang; Lin-Hai Han (Engineering Structures, 2024)

A novel creep contact model for rock and its implement in discrete element simulation - Wengang Zhang; Sicheng Lin; Luqi Wang; Lin Wang; Xiang Jiang; Shuo Wang (Computers and Geotechnics, 2024)

Thermally managed and fireproof composite aerogels for safer and year-round energy saving - Wei Cai; Zhaoxin Li; Heng Xie; Wei Wang; Tianyang Cui; Bicheng Lin; Liangyuan Qi; Xin Hu; Yu Du; Yang Ming; Shuo Shi; Daming Chen; et al. (Chemical Engineering Journal, 2024)

Moderate input of nanoscale zero-valent iron accelerated soil polychlorinated biphenyls dissipation with limited inhibition on arbuscular mycorrhizal fungal diversity - Shuo Wen; Dongnian Sun; Hua Qin; Jingwei Wang; Xiangui Lin; Jianfeng Bai; Junli Hu (Journal of Soils and Sediments, 2024)

Precision co-composting of multi-source organic solid wastes provide a sustainable waste management strategy with high eco-efficiency: a life cycle assessment - Hongge Wang; Zelong Liu; Xuan Wang; Lu Zhang; Xiaofei Wu; Shuo Li; Yubo Cao; Lin Ma (Environmental Science and Pollution Research, 2024)

Emission characteristics of carbonyl compounds from open burning of typical subtropical biomass in South China - Chunlin Zhang; Yiting Cai; Qian Yao; Xiaoting Liu; Lin Song; Jiangyong Li; Shuo Deng; Hao Wang; Boguang Wang (Chemosphere, 2024)

Differentiation of antioxidants in reducing oxidation and improving quality of ready-to-eat roasted shrimp after thermal sterilization - Shuo Wang; Songyi Lin; Rui Liang; Kexin Liu; Xiuhan Chen; Lei Chen; Shuang Li; Na Sun (Food Chemistry, 2024)

Caveolin-1 deficiency alleviates palmitate-induced intracellular lipid accumulation and inflammation in pancreatic β cells - Wen Zeng; Nan Cai; Jia Liu; Kunying Liu; Shuo Lin; Longyi Zeng (Journal of Physiology and Biochemistry, 2024)

Prolonged Exposure to Plant Volatiles does not Significantly Affect Pban Expression and Mating Behavior in Diamondback Moth [Plutella Xylostella (Lepidoptera: Plutellidae)] - Houjun Tian; Ruibin Xu; Heng Li; Shuo Lin; Yixin Chen; Yong Chen; Guang Yang; Hui Wei (Journal of Chemical Ecology, 2024)

Tigecycline-resistance mechanisms and biological characteristics of drug-resistant Salmonella Typhimurium strains in vitro - Lin Li; Longbo Wang; Shuo Yang; Yanfang Zhang; Yiming Gao; Qianyu Ji; Linran Fu; Qiling Wei; Feifei Sun; Shaoqi Qu (Veterinary Microbiology, 2024)

Exploring the chloroplast genomics, comparative analysis, evolution, and phylogenetic relationships of Phylica pubescens (Rhamnaceae) in the Cape Flora - Wenbo Shi; Yahui Huang; Siqi Hu; Huan Wang; Qianhui Lin; Zirui Zhang; Chao Shi; Shuo Wang (South African Journal of Botany, 2024)

Integrating plant microbial fuel cells and permeable O2-releasing rods to enhance copper removal and electricity generation in sediment - Shu-Hui Liu; Jin-Shuo Liu; Chi-Wen Lin (Journal of Water Process Engineering, 2024)

Combined microbe-plant remediation of cadmium in saline-alkali soil assisted by fungal mycelium-derived biochar - Zirun Zhao; Lin Liu; Ying Sun; Liling Xie; Shuo Liu; Mingchun Li; Qilin Yu (Environmental Research, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Toward a mechanistic understanding of Rhenium(VII) adsorption behavior onto aminated polymeric adsorbents: Batch experiments, spectroscopic analyses, and theoretical computations - Shuo Lin; Juan Mao; Jian Xiong; Yuhang Tong; Xiejuan Lu; Tao Zhou; Xiaohui Wu (Chemosphere, 2023)

Promoting electricity generated from sediment-based microbial fuel cells and remediation of copper-containing sediments using plant radial oxygen loss and root exudates - Chi-Wen Lin; Jin-Shuo Liu; Shu-Hui Liu (Process Safety and Environmental Protection, 2023)

Westerly aridity in the western Tarim Basin driven by global cooling since the mid-Pleistocene transition - Hongye Liu; Rui Zhang; Yansheng Gu; Gaowen Dai; Lin Li; Shuo Guan; Zhongbiao Fu (Quaternary Science Reviews, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

Allyl methyl disulfide (AMDS) prevents N,N-dimethyl formamide-induced liver damage by suppressing oxidative stress and NLRP3 inflammasome activation - Long-Xia Li; Lin Wang; Shuo Wang; Xiu-Ning Zhang; Hong Liu; Yan-Jing Zhang; Chuan-Tao Wu; Cui-Li Zhang; Tao Zeng (Food and Chemical Toxicology, 2023)

Hcp1 regulates flagella of Aeromonas veronii TH0426 to reduce virulence - Ying-da Wang; Jin-shuo Gong; Yong-chao Guan; Ze-lin Zhao; Ya-nan Cai; Xiao-feng Shan (Aquaculture, 2023)

Long-term PM2.5 concentration prediction based on improved empirical mode decomposition and deep neural network combined with noise reduction auto-encoder- A case study in Beijing - Mengfan Teng; Siwei Li; Jie Yang; Shuo Wang; Chunying Fan; Yu Ding; Jiaxin Dong; Hao Lin; Shansi Wang (Journal of Cleaner Production, 2023)

Assessing the impact of intermediate import liberalization on green innovation in pollution-prone industries: A study on publicly traded companies - Shuo Tian; Ehsan Elahi; Lin Liu; Ailin Sun (Journal of Cleaner Production, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

Melamine-Ag with dual functions of electrochemiluminescence luminophore and coreactant accelerators: Construction of MIP/M-Ag@MoS2-QDs sensing platform for specific detection of thiabendazole - Haiyang Wang; Lin Cai; Wen Hao; Yuwei Wang; Guozhen Fang; Shuo Wang (Food Chemistry, 2023)

Boron nitride nanoplate-based improvement of the specificity and sensitivity in loop-mediated isothermal amplification for Vibrio parahaemolyticus detection - Yong Li; Shuo Lin; Yuxin Xue; Qianyue Jia; Ye Wang; Yingqiu Xie; Chao Shi; Cuiping Ma (Analytica Chimica Acta, 2023)

Changing maize hybrids helps adapt to climate change in Northeast China: revealed by field experiment and crop modelling - Jin Zhao; Zhijuan Liu; Shuo Lv; Xiaomao Lin; Tao Li; Xiaoguang Yang (Agricultural and Forest Meteorology, 2023)

Mechanisms of high ammonium loading promoted phosphorus release from shallow lake sediments: A five-year large-scale experiment - Shuo-Nan Ma; Yuan-Feng Xu; Hai-Jun Wang; Hong-Zhu Wang; Yan Li; Xu-Meng Dong; Ji-Lin Xu; Qing Yu; Martin Søndergaard; Erik Jeppesen (Water Research, 2023)

Emission characteristics of (halogenated) polycyclic aromatic hydrocarbons during printed circuit board combustion and estimated emission intensity of a typical e-waste dismantling site in South China - Xiang Ge; Muhammad Zaffar Hashmi; Shuo Lin; Zenghua Qi; Yingxin Yu; Taicheng An (Environmental Pollution, 2023)

PLK3 promotes the proneural–mesenchymal transition in glioblastoma via transcriptional regulation of C5AR1 - Shuo Yu; Lin Lv; Yang Li; Qian Ning; Tingting Liu; Tinghua Hu (Molecular Biology Reports, 2023)

Carboxylated cellulose-based aerogel with cellular pores prepared by stir freezing for cationic dye adsorption - Shuo Zhang; Yanqiu Pan; Wei Wang; Runze Lin; Xuewu Liu (Process Safety and Environmental Protection, 2023)

Transcriptomic analysis the mechanisms of anti-osteoporosis of desert-living Cistanche herb in ovariectomized rats of postmenopausal osteoporosis - Shuo Tian; Lin Guo; Yagang Song; Jinxin Miao; Mengfan Peng; Xiaoyan Fang; Ming Bai; Mingsan Miao (Functional & Integrative Genomics, 2023)

Analysis of Nord Stream explosions using seismic recordings - Yang Shen; Xiao-Lin Hu; Tong-Dong Wang; Wei Zhu; Quan-Shi Guo; Shuo Yang; Qiang Lu; De-Zhi Zhang; Wei-Guo Xiao (Applied Geophysics, 2023)

Concatenated dynamic DNA network modulated SERS aptasensor based on gold-magnetic nanochains and Au@Ag nanoparticles for enzyme-free amplification analysis of tetracycline - Yan Lv; Shuo Qi; Imran Mahmood Khan; Xiaoze Dong; Mingwei Qin; Lin Yue; Yin Zhang; Zhouping Wang (Analytica Chimica Acta, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

Quantified trend of photosynthetic rate along the depth of microalgae biofilm - Lin-Lan Zhuang; Wanqing Tian; Yanan Yang; Shuhan Ge; Peihua Li; Shuo Sun; Jian Zhang; Shuang Liang (Science of The Total Environment, 2023)

Enhanced crude oil degradation and reshaped microbial community structure using straw-sludge biochar-persulfate oxidative system in oil-contaminated soil - Qiyou Liu; Fang Tang; Shuo Sun; Yaru Wang; Yuhua Su; Chaocheng Zhao; Xiuxia Zhang; Yingying Gu; Lin Li (Journal of Environmental Chemical Engineering, 2023)

Compositions and sources of sedimentary organic carbon on the tropical epicontinental sea - Baozhi Lin; Zhifei Liu; Meixun Zhao; Penjai Sompongchaiyakul; Hailong Zhang; Thomas M. Blattmann; Shuo Feng; Martin G. Wiesner; Khanh Phon Le; Rithy Meas; Edlic Sathiamurthy (Geochimica et Cosmochimica Acta, 2023)

Sodium alginate/chitosan-based intelligent bilayer film with antimicrobial activity for pork preservation and freshness monitoring - Shenghui Cao; Shuo Wang; Qingqing Wang; Gang Lin; Baolong Niu; Ruijie Guo; Hong Yan; Huifang Wang (Food Control, 2023)

Characteristics of Cloud Water Resource and Precipitation Efficiency of Hydrometeors over Northwest China - Zhanyu Yao; Lin An; Pei Zhang; Liangshu Gao; Shuo Jia; Weijian Wang; Wenhui Zhao (Journal of Meteorological Research, 2023)

Monomethylarsonous acid binds to Cys-104α and Cys-112β of hemoglobin in acute promyelocytic leukemia patients treated with arsenic trioxide - Chunlu Gao; Liwang Lin; Jing Li; Mengliang Wu; Jian Lv; Shuo Tian; Xin Hai (Toxicology Letters, 2023)

Linoleic acid from the endophytic fungus Diaporthe sp. HT-79 inhibits the growth of Xanthomonas citri subsp. citri by destructing the cell membrane and producing reactive oxygen species (ROS) - Huiting Lin; Yan Liang; Kumaravel Kaliaperumal; Qin Xiong; Shuo Duan; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2023)

An efficient cellular image-based platform for high-content screening of neuroprotective agents against chemotherapy-induced neuropathy - Yang-Chen Chang; Yi-Ching Lo; Hsun-Shuo Chang; Hui-Ching Lin; Chien-Chih Chiu; Yih-Fung Chen (NeuroToxicology, 2023)

A novel dehydrocoenzyme activator combined with a composite microbial agent TY for enhanced bioremediation of crude oil-contaminated soil - Qiyou Liu; Shuo Sun; Shuiquan Chen; Yuhua Su; Yaru Wang; Fang Tang; Chaocheng Zhao; Lin Li (Journal of Environmental Management, 2023)

Dual photoluminescence emission carbon dots for ratiometric optical dual-mode and smartphone-integrated visual detection of mercury ion - Dan Chang; Lin Li; Xiaorui Dong; Hu Shi; Shuo Wang; Zhonghua Zhao; Liuliu Lv; Yongxing Yang; Lihong Shi (Journal of Environmental Chemical Engineering, 2023)

Enhanced crude oil degradation by remodeling of crude oil-contaminated soil microbial community structure using sodium alginate/graphene oxide/Bacillus C5 immobilized pellets - Qiyou Liu; Hongxu Chen; Yuhua Su; Shuo Sun; Chaocheng Zhao; Xiuxia Zhang; Yingying Gu; Lin Li (Environmental Research, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

ZIF-8 sacrificial-templated hollow COF architectures enabled highly efficient enrichment, determination and regulation of food hazards from infant formulas - Lu Yang; Lin-Qing Nie; Jing Wang; Chun-Yang Li; Jin Wang; Jing-Min Liu; Shuo Wang (Food Chemistry, 2023)

Modeling collective motion for fish schooling via multi-agent reinforcement learning - Xin Wang; Shuo Liu; Yifan Yu; Shengzhi Yue; Ying Liu; Fumin Zhang; Yuanshan Lin (Ecological Modelling, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

A Data-Driven Intelligent Prediction Approach for Collision Responses of Honeycomb Reinforced Pipe Pile of the Offshore Platform - Lei Yang; Hong Lin; Chang Han; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2023)
The potential collision between the ship and the pipe piles of the jacket structure brings huge risks to the safety of an offshore platform. Due to their high energy-absorbing capacity, honeycomb structures have been widely used as impact protectors in various engineering applications. This paper proposes a data-driven intelligent approach for the prediction of the collision response of honeycomb-reinforced structures under ship collision. In the proposed model, the artificial neural network (ANN) is combined with the dynamic particle swarm optimization (DPSO) algorithm to predict the collision responses of honeycomb reinforced pipe piles, including the maximum collision depth (δmax) and maximum absorption energy (Emax). Furthermore, a data-driven evaluation method, known as grey relational analysis (GRA), is proposed to evaluate the collision responses of the honeycomb-reinforced pipe piles of offshore platforms. Results of the case study demonstrate the accuracy of the DPSO-BP-ANN model, with measured mean-square-error (MSE) of 5.06 × 10−4 and 4.35 × 10−3 and R2 of 0.9906 and 0.9963 for δmax and Emax, respectively. It is shown that the GRA method can provide a comprehensive evaluation of the performance of a honeycomb structure under impact loads. The proposed model provides a robust and efficient assessment tool for the safe design of offshore platforms under ship collisions.

Chemical investigations and cytotoxic effects of metabolites from Antrodia camphorata against human hepatocellular carcinoma cells - Yih-Fung Chen; Ho-Cheng Wu; Jia-Min Chang; Horng-Huey Ko; Chu-Hung Lin; Hsun-Shuo Chang (Natural Product Research, 2023)

A novel chitosan-biochar immobilized microorganism strategy to enhance bioremediation of crude oil in soil - Qiyou Liu; Yaru Wang; Shuo Sun; Fang Tang; Hongxu Chen; Shuiquan Chen; Chaocheng Zhao; Lin Li (Chemosphere, 2023)

A smartphone-assisted optosensing platform based on chromium-based metal-organic framework signal amplification for ultrasensitive and real-time determination of oxytetracycline - Xuelian Hu; Yichuan Cao; Lin Cai; Haiyang Wang; Guozhen Fang; Shuo Wang (Journal of Hazardous Materials, 2023)

Engineering electron redistribution of bimetallic phosphates with CeO2 enables high-performance overall water splitting - Xin Guo; Menggang Li; Longyu Qiu; Fenyang Tian; Lin He; Shuo Geng; Yequn Liu; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2023)

Intraoperative Detection of Surgical Gauze Using Deep Convolutional Neural Network - Shuo-Lun Lai; Chi-Sheng Chen; Been-Ren Lin; Ruey-Feng Chang (Annals of Biomedical Engineering, 2023)

The construction of high efficient visible-light-driven 3D porous g-C3N4/Fe3O4 photocatalyst: A new photo-induced bacterial inactivation material enhanced by cascade photo-Fenton reaction - Ze-Yu Liu; Wen-Qian Huang; Chuan-Qing Huang; Zhao-Zhen Liu; Xiao-Yue Tang; Wei-Chang Chen; Zheng-Zheng Tang; Yu-Xing Huang; Shuo-Chun Zheng; Lin Lin; Changzhu Li; Yong Ye (Chemosphere, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Efficient PPCPs degradation by self-assembly Ag/Ti3C2@BiPO4 activated peroxydisulfate with microwave irradiation: Enhanced adsorptive binding and radical generation - Shuo Li; Fanxue Lin; Heshan Zheng; Yongjie Zheng; Baogang Zhang; Jun Ma; Jun Nan (Chemical Engineering Journal, 2023)

A full range of defect passivation strategy targeting efficient and stable planar perovskite solar cells - Yansen Sun; Shuo Yang; Zhenyu Pang; Haipeng Jiang; Shaohua Chi; Xiaoxu Sun; Lin Fan; Fengyou Wang; Xiaoyan Liu; Maobin Wei; Lili Yang; Jinghai Yang (Chemical Engineering Journal, 2023)

Functionalized photosensitive metal-organic framework as a theranostic nanoplatform for turn-on detection of MicroRNA and photodynamic therapy - Chan Yang; Kun Wang; Shuo Tian; Liuting Mo; Weiying Lin (Analytica Chimica Acta, 2023)

Associations between residential proximity to agricultural land use as pesticides exposure and birth outcomes - Kuna-Chun Chen; Shuo-Fang Lee; Shyang-Woei Lin; Jia-Shan Xie; Yu‐Hsun Chang; Lih-Ming Yiin; Chia-Jung Hsieh (Environmental Science and Pollution Research, 2022)

Numerical Investigation on Performance Optimization of Offshore Sandwich Blast Walls with Different Honeycomb Cores Subjected to Blast Loading - Hong Lin; Chang Han; Lei Yang; Lin Zhang; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
As an important protective facility on offshore platform, the blast wall is of great significance in resisting oil and gas explosions. Honeycomb structures are widely used due to their unique deformation and mechanical properties under dynamic impact loads. The aim of this research is to develop an optimized design for an offshore sandwich blast wall with different honeycomb cores. The uniqueness of this paper is providing the quantitative optimization scheme for topological configurations and unit cell geometric parameters of honeycomb structures according to mass consistency and the proposed synthetic evaluation index of anti-blast performance. By using the numerical simulation software ANSYS/LS-DYNA, the CONWEP algorithm was first validated and then adopted to conduct the dynamical performance analysis of the honeycomb blast wall. For comparison purposes, simulating studies on a series of different blast walls were carried out by considering various influential parameters. According to different criteria, the blast resistance of the sandwich honeycomb structures was evaluated. It is found that the sandwich plate with concave arc honeycomb core has the best anti-blast performance compared to that of arrow honeycomb core and concave hexagonal honeycomb core. For the concave arc honeycomb structure, the geometric parameters such as concave angle and aspect ratio of honeycomb unit cell have great influence on the blast-resistance performance. Moreover, the concave arc honeycomb structure with positive gradient arrangement has better anti-blast performance than the negative one. The curved blast wall with the curvature of 1/20 achieves better anti-blast performance than the flat blast wall.

Dynamic Performance and Crashworthiness Assessment of Honeycomb Reinforced Tubular Pipe in the Jacket Platform under Ship Collision - Hong Lin; Chang Han; Lei Yang; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
The collision between the pipe legs of jacket platforms and bypassing ships is of great concern for the safety assessment of platforms. Honeycomb structures have been widely used owing to their unique deformation and mechanical properties under dynamic impact loads. In this paper, two typical honeycomb structures, namely hexagonal honeycomb and arrow honeycomb, were constructed for the impact protection of inclined pipe legs in jacket platforms, and the present study aimed to assess the dynamical performance and crushing resistance of the designed honeycomb reinforced structure under ship collision by using the numerical simulation software ANSYS/LS-DYNA. The dynamical performance of the honeycomb reinforced pipe leg was investigated considering various influential parameters, including the impact velocity and impact direction. The crashworthiness of the two types of honeycomb was evaluated and compared by different criteria, namely the maximum impact depth (δmax), specific energy absorption (SEA) and the proposed index offset sliding (OS). The results demonstrated that both the hexagonal honeycomb structure and the arrow honeycomb structure can reduce the damage of inclined pipe legs caused by ship collision, while the hexagonal honeycomb can provide the better anti-collision capacity, which can well reduce the offset sliding and better protect the pipe leg from ship collision.

Integrated Analyses of miRNome and Transcriptome Reveal the Critical Role of miRNAs Toward Heat Stress Response in Isochrysis galbana - Jia-Yi Cao; Si-Min Xu; Ying-Ying Wang; Xie-Dan Long; Shuo-Nan Ma; Cheng-Xu Zhou; Ji-Lin Xu; Xiao-Jun Yan (Marine Biotechnology, 2022)

Rhodohalobacter sulfatireducens sp. nov., isolated from a marine solar saltern - Yu-Sheng Wang; Yu-Yan Yue; Yi-Lin Bai; Xu-Yang Zhang; Shuo Wang; Zong-Jun Du (Archives of Microbiology, 2022)

Nitrogen Enrichment Reduces the Diversity of Bacteria and Alters Their Nutrient Strategies in Intertidal Zones - Yuan-Feng Xu; Xu-Meng Dong; Cheng Luo; Shuo-Nan Ma; Ji-Lin Xu; Yong-De Cui (Frontiers in Marine Science, 2022)
Intertidal ecosystems are affected by severe nitrogen (N) pollution as a result of anthropogenic activities, and it is unclear how this may affect intertidal microbial communities, which play critical roles in regulating biogeochemical cycles. To address this gap, we conducted a two-month mesocosm experiment using six targeted concentrations of total N. The findings indicated that N entering seawaters has direct negative effects on the bacterial diversity. Dose dependence was found for the effects of N on bacterial diversity in sediment: low N addition increased the bacterial diversity, but a reduction in bacterial diversity occurred when N exceeded a certain value (≥ 3 mg L−1). Additionally, N enrichment caused clear shifts in bacterial community composition with increases in the relative abundance of Balneola (organic-degrading), Phalacroma mitra (carbohydrate-fermenting), and Bacteroides (phosphorus (P)-solubilizing), and decreases in Leptolyngbya_PPC_6406 (N2-fixing). The increased abundance in P-solubilizing and organic-degrading bacteria and decrease in N-fixing bacteria, combined with the upregulated activity of alkaline phosphatase and downregulation of urease activity, implied that the bacterial assemblage tended to be more effective in P and carbon acquisition but reduced N acquisition. Further path analysis suggested that N had direct effects on bacteria and contributed 50%–100% to the variations in bacterial diversity, whereas environmental changes such as dissolved oxygen and pH played minor roles. Overall, bacteria occurring in sediment were likely more stress-resistant to high N exposure than those occurring in seawater, possibly due to the high buffering capacity of sediment and growth tolerances of bacteria in the sediment. These findings point to the vulnerability of microbes in water systems to increasing global N loading, and that N reduction is needed to combat the loss of microbial diversity.

Intelligent identification method and application of seismic faults based on a balanced classification network - Jing Yang; Ren-Wei Ding; Hui-Yong Wang; Nian-Tian Lin; Li-Hong Zhao; Shuo Zhao; Yu-Jie Zhang (Applied Geophysics, 2022)

Baculoviruses hijack the visual perception of their caterpillar hosts to induce climbing behaviour thus promoting virus dispersal - Xiaoming Liu; Zhiqiang Tian; Limei Cai; Zhongjian Shen; J. P. Michaud; Lin Zhu; Shuo Yan; Vera I. D. Ros; Kelli Hoover; Zhen Li; Songdou Zhang; Xiaoxia Liu (Molecular Ecology, 2022)
Baculoviruses can induce climbing behaviour in their caterpillar hosts to ensure they die at elevated positions to enhance virus transmission, providing an excellent model to study parasitic manipulation of host behaviour. Here, we demonstrate that climbing behaviour occurred mostly during daylight hours, and that the height at death of Helicoverpa armigera single nucleopolyhedrovirus (HearNPV)‐infected larvae increases with the height of the light source. Phototaxic and electroretinogram (ERG) responses were enhanced after HearNPV‐infection in host larvae, and ablation of stemmata in infected larvae prevented both phototaxis and climbing behaviour. Through transcriptome and quantitative PCR, we confirmed that two opsin genes (a blue light‐sensitive gene, HaBL ; and a long wave‐sensitive gene, HaLW ) as well as the TRPL (transient receptor potential‐like channel protein) gene, all integral to the host's visual perception pathway, were significantly upregulated after HearNPV infection. Knockout of HaBL , HaLW , or TRPL genes using the CRISPR/Cas9 system resulted in significantly reduced ERG responses, phototaxis, and climbing behaviour in HearNPV‐infected larvae. These results reveal that HearNPV alters the expression of specific genes to hijack host visual perception at fundamental levels—photoreception and phototransduction—in order to induce climbing behaviour in host larvae.

Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Po-Yu Liu; Sung-Yin Yang; Chih-Ying Lu; Naohisa Wada; Stéphane De Palmas; Shu-Shuo Yeh; Hideyuki Yamashiro; Sen-Lin Tang; Shan-Hua Yang (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.

Regional characteristics and exploitation potential of atmospheric water resources in China - Lin An; Zhanyu Yao; Pei Zhang; Shuo Jia; Jieyun Zhao; Liangshu Gao; Zhen Liu (International Journal of Climatology, 2022)
The atmospheric water resources (AWR) in China have evident regional characteristics. In order to scientifically and rationally exploit the AWR in different regions of China, we divided China into seven regions based on the ERA‐5, the CloudSat data, and so on. Such characteristics as water vapour, cloud characteristics, cloud water resources (CWR), precipitation efficiency of hydrometeors (PEh), and the exploitation potential of CWR were studied in this article. Some results in summer are shown. (a) There were relatively more precipitation, richer water vapour, stronger water vapour transport and convergence, more cloud covers, and relatively larger zones of rich total column cloud water content in China. Therefore, it is of important significance to study AWR in summer in China. (b) In respect of single‐layer clouds, low clouds were in the majority over the Tibetan Plateau (TP) and the southwest China (SW), medium clouds were predominant over the northern regions, and high clouds existed more over the central region (CR) and the southeast China (SE). The liquid water content (LWC) at each height of cloud was less than 800 mg·m −3 and decreased gradually with the increase in height in China. The convective development heights, the LWC at each altitude, and the frequencies of less LWCs over the northern regions were lower than those over the southern regions. The ice water content (IWC) at each height of cloud was less than 250 mg·m −3 , and more than 96% of them were less than 100 mg·m −3 . (c) CWR over the northeast China (NE), north China (NC), and CR were relatively rich, but with relatively low PEh, so there was relatively higher exploitation potential of CWR in these regions, followed by the northwest China (NW) and TP, and there was still some exploitation potential of CWR in SE and SW.

The Beneficial Role of Exercise on Treating Alzheimer’s Disease by Inhibiting β-Amyloid Peptide - Zi-Xuan Tan; Fang Dong; Lin-Yu Wu; Ya-Shuo Feng; Feng Zhang (Molecular Neurobiology, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Development of a dual-labeled, hydrolysis probe-based, real-time quantitative PCR assay for detection of both genotypes of duck circovirus-1 (DuCV-1) and DuCV-2 - Lin Zhang; Wenming Jiang; Fuyou Zhang; Yang Li; Jinping Li; Shaobo Liang; Xiaohui Yu; Cheng Peng; Shuo Liu; Jingjing Wang; Shuhong Sun; Hualei Liu (Virus Genes, 2021)

Patient Confidential Information Transmission Using the Integration of PSO-Based Biomedical Signal Steganography and Threshold-Based Compression - Shih-Ying Chen; Shan-Ju Lin; Ming-Cheng Tsai; Ming-Dar Tsai; Yih-Jing Tang; Shuo-Tsung Chen; Li-Hsiang Wang (Journal of Medical and Biological Engineering, 2021)

The mechanism and application of high-pressure water jet technology to prevent compound dynamic disaster - Zeng-qiang Yang; Chang Liu; Feng-shuo Li; Lin-ming Dou; Gang-wei Li; Da-wei Wang (Arabian Journal of Geosciences, 2021)

Effect of Calcium-Based Catalysts on Pyrolysis Liquid Products from Municipal Sludge - Wei Luo; Yi-Feng Su; Qing Hu; Huai-Lin Yin; Shuo Wang; Li-Jiao Ao; Xiao-Xi Wen; Sheng-Xiong Huang; Nan Zhou; Wei Zhang; Zhi Zhou (BioEnergy Research, 2020)

Neuroimaging Spectrum at Pre-, Early, and Late Symptomatic Stages of SCA17 Mice - Chiao-Chi Chen; Nai-Wei Yao; Chia-Wei Lin; Wei-Shuo Su; Chin-Tien Wu; Chen Chang; Hsiu Mei Hsieh-Li (The Cerebellum, 2020)

Bias Adjustment of Satellite Precipitation Estimation Using Ground-Based Observation: Mei-Yu Front Case Studies in Taiwan - Nan-Ching Yeh; Yao-Chung Chuang; Hsin-Shuo Peng; Kuo-Lin Hsu (Asia-Pacific Journal of Atmospheric Sciences, 2020)
The Global Satellite Mapping of Precipitation (GSMaP) was used to estimate the accumulated rainfall in May from the Mei-Yu front in Taiwan. Rainfall estimation from GSMaP during 2002–2017 were evaluated using more than 400 local gauge observations, collected from the Taiwan Central Weather Bureau (CWB). Studies have demonstrated that the GSMaP rainfall estimation estimates can be biased, depending on the target region, elevation, and season. In this experiment, we have evaluated GSMaP over three elevation ranges. The GSMaP systemic errors for each elevation range were identified and corrected using regression analysis. The results indicated that GSMaP estimation can be improved significantly through adjustment over three elevation ranges (elevation less than 50 m, elevation of 50–100 m, and elevation higher than 100 m). For these three elevation ranges, the correlation coefficient between the GSMaP estimations and CWB rainfall data was 0.76, 0.78, and 0.59, respectively. This indicated that the GSMaP estimation was more accurate for low-elevation regions than high-elevation regions. After the proposed approaches were employed to correct the errors, the bias errors were respectively improved by 5.64(13.7%), 7.33(38.4%) and 10.52(31.2%) mm for low-, mid- and high-elevation regions. This study demonstrated that the local correction approaches can be used to improve GSMaP estimation of Mei-Yu rainfall in Taiwan.

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

Adsorptive removal of cationic tricyclic antidepressants using cation-exchange resin - Jong-Won Choi; John Kwame Bediako; Yufeng Zhao; Shuo Lin; Amit Kumar Sarkar; Minhee Han; Myung-Hee Song; Chul-Woong Cho; Yeoung-Sang Yun (Environmental Science and Pollution Research, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Evaluation of orange peel-derived activated carbons for treatment of dye-contaminated wastewater tailings - John Kwame Bediako; Shuo Lin; Amit Kumar Sarkar; Yufeng Zhao; Jong-Won Choi; Myung-Hee Song; Chul-Woong Cho; Yeoung-Sang Yun (Environmental Science and Pollution Research, 2020)

Predicting 3D heterogeneous in situ stress field of Gaoshangpu Oilfield northern area, Nanpu Sag, Bohai Bay Basin, China - Ke Xu; Junsheng Dai; Jianwei Feng; Bifeng Wang; Lin Shang; Lu Fang; Shuo Wang (Arabian Journal of Geosciences, 2020)

Secondary metabolites from the fermented rice of the fungus Monascus purpureus and their bioactivities - Ho-Cheng Wu; Ming-Jen Cheng; Ming-Der Wu; Jih-Jung Chen; Yen-Lin Chen; Hsun-Shuo Chang; Kai-Ping Chen (Natural Product Research, 2019)

First Report on Toxoplasma gondii Seroprevalence in Free-Ranging Pigs in Northeastern China - Qi Li; Si-Yuan Qin; Shuo Li; Peng Peng; Quan Zhao; Hong-Lin Jia; Chun-Ren Wang (Acta Parasitologica, 2019)

Transcription Factor 2I Regulates Neuronal Development via TRPC3 in 7q11.23 Disorder Models - Marielle H. S. Deurloo; Ekaterina Turlova; Wen-Liang Chen; You Wei Lin; Elaine Tam; Nardos G. Tassew; Michael Wu; Ya-Chi Huang; Jacqueline N. Crawley; Philippe P. Monnier; Alexander J. A. Groffen; Hong-Shuo Sun; et al. (Molecular Neurobiology, 2019)

NMDA Receptor Antagonist MK801 Protects Against 1-Bromopropane-Induced Cognitive Dysfunction - Lin Xu; Xiaofei Qiu; Shuo Wang; Qingshan Wang; Xiu-Lan Zhao (Neuroscience Bulletin, 2019)

Declining hailstorm frequency in China during 1961–2015 and its potential influential factors - Wenhui Zhao; Jianping Guo; Zhanyu Yao; Yuxing Yun; Shuo Jia; Weijian Wang; Pei Zhang; Hui Xu; Huan Liu; Liangshu Gao; Yanluan Lin; Mingxin Li; et al. (International Journal of Climatology, 2018)
Based on 55 years (from 1961 to 2015) of ground‐based hailstorm and atmospheric sounding observations, the climatological characteristics of hailstorms in China, along with potential influencing factors, were analysed. We found that hailstorms exhibit large spatial and temporal variability, with the peak occurring in spring in south China, and in summer in north China. The Tibetan Plateau (TTP) is a region with high hailstorm frequency. Overall, the frequency of hailstorms has decreased over the 55 years, although there was an increase from 1961 to 1985. In terms of diurnal variability, while hailstorm frequency peaks in the afternoon in most of China, it peaks during the night or early morning in southwest China. The magnitude of the peak increased during the 1960s and 1970s, and then decreased afterwards. Hailstorms are negatively correlated with daily mean temperature but are positively correlated with diurnal temperature range, convective available potential energy (CAPE) and totals–totals index. The increase of hailstorms during the period from 1961 to 1985 is mainly correlated with the increase in CAPE over the TTP region, while the decrease of hailstorms afterwards is correlated with all four convective parameters. The finding has significant implications for the potential impact of increasing greenhouse gases on climatological changes in hailstorm.

Investigation on pseudorabies prevalence in Chinese swine breeding farms in 2013–2016 - Yingyi Liu; Shuo Zhang; Qi Xu; Jiajun Wu; Xinyan Zhai; Shuo Li; Jing Wang; Jianqiang Ni; Lin Yuan; Xiaohui Song; Bolin Zhao; Zhi Zhou; et al. (Tropical Animal Health and Production, 2018)

Climate zones determine where substantial increases of maize yields can be attained in Northeast China - Zhijuan Liu; Xiaoguang Yang; Xiaomao Lin; Prasanna Gowda; Shuo Lv; Jing Wang (Climatic Change, 2018)

Variations of Laohugou Glacier No. 12 in the western Qilian Mountains, China, from 1957 to 2015 - Yu-shuo Liu; Xiang Qin; Ji-zu Chen; Zhen-lin Li; Jing Wang; Wen-tao Du; Wan-qin Guo (Journal of Mountain Science, 2018)

Two cultivated legume plants reveal the enrichment process of the microbiome in the rhizocompartments - Xiao Xiao; Weimin Chen; Le Zong; Jun Yang; Shuo Jiao; Yanbing Lin; Entao Wang; Gehong Wei (Molecular Ecology, 2017)
The microbiomes of rhizocompartments (nodule endophytes, root endophytes, rhizosphere and root zone) in soya bean and alfalfa were analysed using high‐throughput sequencing to investigate the interactions among legume species, microorganisms and soil types. A clear hierarchical filtration of microbiota by plants was observed in the four rhizocompartments – the nodule endosphere, root endosphere, rhizosphere and root zone – as demonstrated by significant variations in the composition of the microbial community in the different compartments. The rhizosphere and root zone microbial communities were largely influenced by soil type, and the nodule and root endophytes were primarily determined by plant species. Diverse microbes inhabited the root nodule endosphere, and the corresponding dominant symbiotic rhizobia belonged to Ensifer for alfalfa and Ensifer – Bradyrhizobium for soya bean. The nonsymbiotic nodule endophytes were mainly Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes. The variation in root microbial communities was also affected by the plant growth stage. In summary, this study demonstrated that the enrichment process of nodule endophytes follows a hierarchical filtration and that the bacterial communities in nodule endophytes vary according to the plant species.

Temporal dynamics of microbial communities in microcosms in response to pollutants - Shuo Jiao; Zhengqing Zhang; Fan Yang; Yanbing Lin; Weimin Chen; Gehong Wei (Molecular Ecology, 2017)
Elucidating the mechanisms underlying microbial succession is a major goal of microbial ecology research. Given the increasing human pressure on the environment and natural resources, responses to the repeated introduction of organic and inorganic pollutants are of particular interest. To investigate the temporal dynamics of microbial communities in response to pollutants, we analysed the microbial community structure in batch microcosms that were inoculated with soil bacteria following exposure to individual or combined pollutants (phenanthrene, n ‐octadecane, phenanthrene + n ‐octadecane and phenanthrene + n ‐octadecane + CdCl 2 ). Subculturing was performed at 10‐day intervals, followed by high‐throughput sequencing of 16S r RNA genes. The dynamics of microbial communities in response to different pollutants alone and in combination displayed similar patterns during enrichment. Specifically, the repression and induction of microbial taxa were dominant, and the fluctuation was not significant. The rate of appearance for new taxa and the temporal turnover within microbial communities were higher than the rates reported in other studies of microbial communities in air, water and soil samples. In addition, conditionally rare taxa that were specific to the treatments exhibited higher betweenness centrality values in the co‐occurrence network, indicating a strong influence on other interactions in the community. These results suggest that the repeated introduction of pollutants could accelerate microbial succession in microcosms, resulting in the rapid re‐equilibration of microbial communities.

FUS-linked essential tremor associated with motor dysfunction in Drosophila - Murni Tio; Rujing Wen; Yih Lin Lim; Huashan Wang; Shuo-Chien Ling; Yi Zhao; Eng-King Tan (Human Genetics, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

Functional architecture of two exclusively late stage pollen-specific promoters in rice (Oryza sativa L.) - Shuo Yan; Zhongni Wang; Yuan Liu; Wei Li; Feng Wu; Xuelei Lin; Zheng Meng (Plant Molecular Biology, 2015)

Sassarandainol: a new neolignan and anti-inflammatory constituents from the stem of Sassafras randaiense - Ya-Ling Hou; Hsun-Shuo Chang; Hui-Chun Wang; Sheng-Yang Wang; Tze-Ying Chen; Chu-Hung Lin; Ih-Sheng Chen (Natural Product Research, 2015)

Altered splenic miRNA expression profile in H1N1 swine influenza - Liangzong Huang; Jun Ma; Yankuo Sun; Yanli Lv; Wen Lin; Mingjie Liu; Changsong Tu; Pei Zhou; Wanjun Gu; Shuo Su; Guihong Zhang (Archives of Virology, 2015)

Residues and dissipation of trifloxystrobin and its metabolite in tomatoes and soil - Lin Wang; Wenming Li; Puyu Li; Minghui Li; Shuo Chen; Lijun Han (Environmental Monitoring and Assessment, 2014)

The heparan sulfate proteoglycan agrin contributes to barrier properties of mouse brain endothelial cells by stabilizing adherens junctions - Esther Steiner; Gaby U. Enzmann; Ruth Lyck; Shuo Lin; Markus A. Rüegg; Stephan Kröger; Britta Engelhardt (Cell and Tissue Research, 2014)

Amphipol-Trapped ExbB–ExbD Membrane Protein Complex from Escherichia coli: A Biochemical and Structural Case Study - Aleksandr Sverzhinsky; Shuo Qian; Lin Yang; Marc Allaire; Isabel Moraes; Dewang Ma; Jacqueline W. Chung; Manuela Zoonens; Jean-Luc Popot; James W. Coulton (The Journal of Membrane Biology, 2014)

Cloning and gene expression analysis of sponge gourd ascorbate peroxidase gene and winter squash superoxide dismutase gene under respective flooding and chilling stresses - Chih Ming Chiang; Wen Shuo Kuo; Kuan Hung Lin (Horticulture, Environment, and Biotechnology, 2014)

Synthesis and analgesic evaluation of a series of proline-typed spiro cyclic quaternary ammoniums - Songwen Lin; Na Wang; Shuo Zhao; Qi Sun; Weiwei Zhang; Jia Ye; Tieming Cheng; Runtao Li (Medicinal Chemistry Research, 2014)

Triacylglycerol accumulation of Phaeodactylum tricornutum with different supply of inorganic carbon - Xiaowei Peng; Shuo Liu; Wei Zhang; Yonggang Zhao; Lin Chen; Hui Wang; Tianzhong Liu (Journal of Applied Phycology, 2014)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Production, purification and characterization of a thermostable laccase from a tropical white-rot fungus - Li-Qiong Guo; Shuo-Xin Lin; Xiao-Bing Zheng; Zi-Rou Huang; Jun-Fang Lin (World Journal of Microbiology and Biotechnology, 2011)

Analysis of the Composition and Characteristics of Culturable Endophytic Bacteria Within Subnival Plants of the Tianshan Mountains, Northwestern China - Hong Mei Sheng; Hong Shan Gao; Lin Gui Xue; Shuo Ding; Chun Li Song; Hu Yuan Feng; Li Zhe An (Current Microbiology, 2011)

The effect of excess expression of GFP in a novel heart-specific green fluorescence zebrafish regulated by nppa enhancer at early embryonic development - Wen Huang; Yun Deng; Wei Dong; Wuzhou Yuan; Yongqi Wan; Xiaoyan Mo; Yongqing Li; Zequn Wang; Yuequn Wang; Karen Ocorr; Bo Zhang; Shuo Lin; et al. (Molecular Biology Reports, 2011)

Tolerance and accumulation of lead by species of Iris L. - Yu-Lin Han; Su-Zhen Huang; Ji-Guang Gu; Shuo Qiu; Jie-Min Chen (Ecotoxicology, 2008)

Isolation and characterization of a novel thermophilic Bacillus strain degrading long-chain n-alkanes - Lei Wang; Yun Tang; Shuo Wang; Ru-Lin Liu; Mu-Zhi Liu; Yan Zhang; Feng-Lai Liang; Lu Feng (Extremophiles, 2006)

Protein and mRNA characterization in high and low metastasis adenoid cystic carcinoma cell lines - Jie-lin Yang; Nai-shuo Zhu; Ying Wang; Xiao-feng Guan; Zhao-xin Zheng (Molecular Biology Reports, 2005)

Detailed Computational Analysis of a Comprehensive Set of Group A Rotavirus NSP4 Proteins - Shuo Liang Lin; Peng Tian (Virus Genes, 2003)

C-met activation is necessary but not sufficient for liver colonization by B16 murine melanoma cells - Shuo Lin; Dario Rusciano; Patrizia Lorenzoni; Guido Hartmann; Walter Birchmeier; Silvia Giordano; Paolo Comoglio; Max M. Burger (Clinical & Experimental Metastasis, 1998)